Coated metal foil of copper or copper alloy and method for producing coated metal foil of copper or copper alloy
By coating the composition of organic wax cleavage agent and copper or copper alloy sheets on the surface of copper or copper alloy metal foil, the problem of thermal mechanical fracture of TLP bonding joint and high cost of silver sintered joint in the prior art is solved, and an efficient and economical high-temperature bonding effect is achieved.
Patent Information
- Application Number
- CN202480003608.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-08
- Filing Date
- 2024-03-11
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, when achieving high temperature bonding, the thermomechanical fracture behavior of the TLP bonding joint has disadvantages, and the silver sintered joint has high cost and low electromobility, making it difficult to meet the requirements of wide bandgap semiconductor devices.
Using copper metal foil or copper alloy metal foil, a porous microstructure is formed by coating the surface of the composition of organic binder and copper sheet or copper alloy sheet to achieve a short sintering time, low sintering temperature and low sintering pressure.
The copper-containing intermediate layer has high thermal mechanical fatigue resistance, thermal conductivity and electrical conductivity, and the residual organic matter is low during the sintering process, which is suitable for large-scale production.
Smart Images

Figure CN119654205A_ABST
Abstract
Description
[0001] The present invention relates to a copper-coated metal foil or a copper alloy-coated metal foil for forming a copper-containing intermediate layer between a first solid substrate and a second solid substrate, a method for producing a copper-coated metal foil or a copper alloy-coated metal foil, and the use of the copper-coated metal foil or the copper alloy-coated metal foil. In the sense of the present invention, the intermediate layer is understood to be an interconnection layer, i.e. a solid metal interconnection between the first solid substrate and the second solid substrate.
[0002] Die-attach bonding is a key process to enable high temperature operation of power semiconductor devices. For the past few decades, high-lead solder has been the preferred and recognized choice. However, strict regulations regarding hazardous substances have restricted the use of high-lead solder, and the few exceptions that currently exist are expected to be banned in the near future. With the increasing use of wide-bandgap (WBG) semiconductor devices, there is a need to find sustainable and reliable alternatives at both the economic and technological frontiers. Interconnect materials and technologies need to be able to meet the challenging requirements of WBG semiconductor devices while being economical to achieve large-scale production.
[0003] Currently, there are two established methods that produce high-temperature bonds while benefiting from relatively low bonding temperatures: transient liquid phase (TLP) bonding and particle sintering. Although various studies have reported successful in-situ phase production with higher remelting points, the thermomechanical fracture behavior of TLP bonded joints seems to have a major disadvantage. This is due to the microstructure of the TLP bonded joint, as it is made of brittle intermetallic compounds (IMC). However, in the case of particle sintering, silver (Ag) sintered joints have been reported as promising candidates for high-temperature WBG applications. During the sintering process, a through-connection consisting of one metal can be achieved. In addition to the high thermal conductivity of the material, the advantage is that the interconnection is established at a relatively low temperature (250°C) but is stable at higher temperatures (over 300°C). However, sintering silver particles has its own disadvantages: high cost and low resistance to electromigration.
[0004] Copper is approximately 100 times cheaper than silver, as well as being more abundant, easily recyclable and readily available. Copper has an overall lower carbon footprint than silver. It has a lower coefficient of thermal expansion than silver and has nearly identical electrical and thermal conductivity. However, copper has a higher melting point, which means that its sintering temperature is also slightly higher than silver. Additionally, susceptibility to rapid oxidation in the atmosphere is a major disadvantage when using copper, as this is detrimental to the mechanical and thermal integrity of the joint.
[0005] According to Bhogaraju, SK et al., “Novel approach to copper sintering using surface enhanced brass micro flakes for microelectronics packaging”, Journal of Alloys and Compounds, Volume 844, 2020, 156043, etched copper flakes or brass flakes are mixed with PEG600 as a binder to obtain a paste preparation. Prior to preparing the paste preparation, the flakes are treated with 12M HCl to etch zinc from the brass flakes and copper oxides from the copper flakes. After etching, the flakes are first thoroughly rinsed in distilled water and then in isopropanol. This treatment removes zinc, chlorine, and all organic components from the flakes. The use of PEG600 in the paste preparation reportedly ensures in-situ reduction of copper oxides during sintering.
[0006] Bhogaraju, SK et al., in "Die-attach bonding with etched micro brass metal pigment flakes for high-power electronics packaging", ACS Appl. Electron. Mater. 2021, 3, 10, 4587-4603, disclose a sintering paste consisting of etched micro brass metal pigment flakes or pure copper flakes and a binder mixture of α-pinene alcohol and polyethylene glycol 600 (PEG600). Prior to preparing the paste, the flakes were treated with HCl for etching, washed in distilled water, washed in isopropanol, and dried in air. This treatment removes zinc, chlorine, and all organic components from the flakes.
[0007] EP 3 626 785 B1 discloses a metal paste comprising 65 to 85 wt % of metal particles and 10 to 35 wt % of an organic solvent, wherein 70 to 100 wt % of the metal particles consist of organically coated copper flakes comprising 1.9 m 2 / g to 3.7m 2 The organic coating layer may be selected from the group consisting of a specific surface area in the range of 1 wt % to 5 wt %, a total oxygen content in the range of 2 wt % to 4 wt %, and a total carbon to total oxygen weight ratio in the range of 0.25 to 0.9. The organic coating layer may have a ratio in the range of 2 wt % to 5 wt % based on the weight of the organic-coated copper flake.
[0008] WO 2006 / 041657 A2 discloses a method for making a conductive feature on a substrate, the method comprising the steps of: (a) providing a precursor composition comprising a copper metal precursor compound, wherein the viscosity of the precursor composition is no greater than 1000 centipoise; (b) depositing the precursor composition on the substrate using a direct-write tool; and (c) heating the precursor composition to a conversion temperature no greater than about 350° C. to form a conductive feature having a resistivity no greater than about 40 times the resistivity of bulk copper. The substrate may be selected from the group consisting of polyfluorinated compounds, polyimides, epoxies (including glass-filled epoxies), polycarbonates, cellulose-based materials (i.e., wood or paper), acetates, polyesters, polyethylene, polypropylene, polyvinyl chloride, acrylonitrile, butadiene (ABS), flexible fiberboard, non-woven polymer fabrics, cloth and metal foils, semiconductors, ceramics, glass, and combinations thereof. In addition, a method for manufacturing copper conductive features on a substrate surface is disclosed, comprising the following steps: (a) providing a precursor composition comprising a copper metal precursor compound, wherein the viscosity of the precursor composition is no greater than 100 centipoise; (b) depositing the precursor composition on the substrate using an aerosol spray device to form a trace having a minimum dimension no greater than about 100 microns; and (c) heating the precursor composition to a temperature no greater than about 250° C. to form a conductive feature having a minimum feature dimension no greater than about 100 microns and a resistivity no greater than about 100 times the resistivity of bulk copper metal.
[0009] Lin CT et al., "Effect of surfactant on casting metalorganic films and writing copper metal patterns", J. Mater. Res., 6 (4), April 1991, 760-765, disclose the introduction of Triton X-100 detergent into a metal organic solution and the application of the detergent / metal organic solution to a substrate to form a uniform spin-coated film. A metal organic solution prepared from a solvent mixture of methanol and Triton X-100 (volume ratio 50:1) was spin-deposited as a copper formate film precursor. Copper patterns were directly written on glass and polyimide substrates using a KrF laser (248 nm).
[0010] CN 104341860 A discloses a nano conductive ink and a preparation method thereof, wherein the nano conductive ink comprises an organic copper salt, a solvent, a surfactant and nano metal conductive particles. The preparation method comprises: step 1, uniformly mixing the organic copper salt, the solvent, the surfactant and the nano metal conductive particles in a certain proportion to form a solution; step 2, filtering the solution obtained in step 1 through a sieve to obtain the nano conductive ink.
[0011] US2006 / 0258136 A1 discloses a method for forming metal traces on a substrate. The method includes inkjet printing a chemical ink including a metal compound on a substrate surface to form ink droplets thereon, and heating the substrate to a suitable high temperature. The ink droplets undergo at least one of decomposition and reduction due to the substrate temperature, forming metal on the substrate in a controlled atmosphere.
[0012] Die Top System distributed by Heraeus Electronics It consists of a copper foil (on one side of which is plated with NiPdAu-, NiAu- or NiAg) and a silver-based sintering paste pre-applied on the plated layer. They can be sintered together in one step using standard sintering equipment.
[0013] The problem solved by the present invention is to provide an optional interconnect material, a method for producing the optional interconnect material and the use of the optional interconnect material. The optional interconnect material should allow bonding, in particular for die-top side attach, first-level interconnect (i.e., chip to substrate) and second-level interconnect (i.e., substrate to base plate), to form an electrically conductive and / or thermally conductive path and substrate attachment on a solid substrate. The optional interconnect material should ensure sintering with a short sintering time, a low sintering temperature and / or a low sintering pressure. The sintering of the optional interconnect material should make the copper-containing intermediate layer have very good thermomechanical fatigue resistance, high thermal conductivity and high electrical conductivity. In addition, the sintering of the optional interconnect material should produce a uniform bonding interface.
[0014] This problem is solved by the subject matter of claims 1, 12 and 16. Embodiments of the invention are the subject matter of claims 2 to 11 and claims 13 to 15.
[0015] According to the present invention, a coated metal foil is provided, which is used to form a copper-containing intermediate layer between a first solid substrate and a second solid substrate or between a solid substrate and a metal foil. The coated metal foil comprises or consists of: a copper metal foil or a first copper alloy metal foil or a copper metal foil plated with a nickel-iron alloy, wherein the metal foil has a first surface and a second surface, and a composition coated on the first surface and / or the second surface of the metal foil. The composition comprises or consists of the following components: an organic binder and a copper sheet, a first copper alloy sheet or a second copper alloy sheet, wherein the sheet comprises internal pores.
[0016] In the present application, the term "metal foil" refers to the metal foil itself, i.e. without coating the composition on the first surface and / or the second surface of the metal foil. However, organic residues remaining on the foil due to standard production processes may be present on the foil. The organic residues may be oil.
[0017] The metal foil having the coating provided by the composition is designated as "coated metal foil". The metal foil and sheet are formed of an elemental metal, that is, a metal in its elemental form, rather than in its ionic form. The metal is copper or a copper alloy. In the case of a metal foil, the metal may also be copper coated with a nickel-iron alloy. The nickel-iron alloy may be FeNi36, commonly referred to as Copper foil coated with nickel-iron alloy is usually coated on both sides of the copper. Applications with low thermal expansion coefficient are of particular interest for this FeNi36 based foil. It can be a commercially available foil such as CIC Foil in which the core layer is made of an iron-nickel alloy with a nickel content of 36%, and the core layer accounts for 60% of the composite volume. The copper on either side accounts for 20% of the composite volume. This foil can be purchased commercially from Schlenk Metallfolien GmbH & Co. KG, Germany as CIC 20 / 60 / 20.
[0018] The inventors of the present invention have found that the coated metal foil according to the present invention can be manufactured by using standard metal foils with various material properties (e.g., various tensile strengths) or thicknesses. It is very advantageous that the material properties of the coated metal foil according to the present invention can be fine-tuned in this way to adapt to the requirements of its desired application. By coating the metal foil with a composition comprising a thin sheet with internal pores, a porous microstructure can be provided to supplement the material properties of the metal foil. The thickness of the coating can be independently varied on either side of the metal foil by suitable standard application methods, such as screen printing, stencil printing, spraying or spin coating. All of this ensures that the interconnection, its thickness and its resistance to thermomechanical fatigue are fine-tuned. Therefore, the requirements of specific applications and / or specific packaging can be met.
[0019] Furthermore, the coated metal foil according to the invention ensures sintering with short sintering times, low sintering temperatures and / or low sintering pressures. Since organic binders usually evaporate or decompose at temperatures applied before or at the beginning of the sintering process, the coated copper-containing metal foil according to the invention ensures sintering with low residual organic matter. Therefore, the coated metal foil can also be used for specific applications, in which relatively low sintering pressures, in particular pressures of up to 250 kPa, and relatively low sintering temperatures, in particular temperatures of up to 260° C., are applied. In order to achieve miniaturization in specific applications, such as in batteries or high-power light-emitting diodes, the metal foil can be an ultra-thin metal foil with a thickness of less than 10 μm. On the foil, a thin layer of the composition can be applied on the first surface and / or the second surface to produce a low bond line thickness, such as a bond line thickness of less than 5 μm. The bond line thickness is the thickness of the intermediate layer between the first solid substrate and the second solid substrate.
[0020] The composition may be applied to the first surface, and an additional composition may be applied to the second surface. The additional composition comprises or consists of: the organic binder or an additional organic binder; and a sheet of copper, a first copper alloy, or a second copper alloy, or an additional sheet, wherein the additional sheet comprises internal pores.
[0021] By coating a first surface with a composition and a second surface with a further composition, each of these compositions can be adapted to the specific requirements of each surface. For example, in a method for producing a coated metal foil, when the first surface is in a more oxidized state than the second surface, the composition of the composition can be more suitable than the further composition for in situ reduction of copper oxide. In this case, the further composition does not necessarily contain as much reducing organic binder, such as a diol or polymeric diol, as the composition.
[0022] The grains in the metal foil at the first surface and / or the second surface of the metal foil may have an average grain size of at least 2 μm and at most 100 μm. The grains in the thin sheet and / or the further thin sheet may independently of one another have an average grain size of at least 5 nm and at most 200 nm, in particular at least 20 nm and at most 200 nm. A grain is any crystallite constituting a solid metal. In the case of the first surface and / or the second surface, the metal is copper or a first copper alloy or a second copper alloy.
[0023] The term "average grain size" refers to the average grain size given as an average diameter, which is determined by the average area determined by the electron backscatter diffraction technique (EBSD) according to ISO / DIS 13067 (en). It is a value determined by a two-dimensional measurement and is related to the average three-dimensional size of a collection of grains or crystals that form a polycrystalline material by stereological relationships. The collection of grains or crystals may include 30 to 1000, in particular 40 to 400, in particular 50 to 200 grains or crystals.
[0024] Grain boundaries serve as pathways for diffusion of atoms or molecules during sintering. During sintering, as sintering temperature is applied, atoms or molecules migrate across these boundaries, thereby improving diffusion and, in turn, the sintering process. It has been found that a given average grain size results in relatively fast sintering and a relatively high densification rate.
[0025] In one embodiment, the ratio of the average grain size of the grains in the thin sheet to the average grain size of the grains at the first surface and / or the second surface of the metal foil does not exceed 0.002, and / or the ratio of the average grain size of the grains in the additional thin sheet to the average grain size of the grains at the second surface of the metal foil does not exceed 0.002, each of the above situations being independent of each other.
[0026] The effect of this ratio is that it creates an energy change between the surface of the thin sheet or further thin sheet and the first and / or second surface of the metal foil. This is because the thin sheet or further thin sheet has more grains in the same volume than the foil at its first and / or second surface, and thus also has more grain boundaries than the foil at its first and / or second surface, and this difference in the number of grain boundaries enhances surface diffusion and sintering between the thin sheets. The smaller grains of the thin sheet tend to densify faster than the larger grains at the first and / or second surface of the metal foil. Therefore, there is a difference between the sintering of the thin sheet and the sintering of the first and / or second surface of the metal foil. In this way, the mechanical properties of the copper foil can be maintained and contribute to the mechanical properties of the sintered thin sheet.
[0027] The first copper alloy may be bronze or brass. If the metal forming the metal foil is the first copper alloy, the coated metal foil according to the present invention can have good thermal conductivity. When the metal forming the metal foil is copper, a higher thermal conductivity of the coated metal foil according to the present invention can be obtained. Brass may be a brass containing at least 0.5% by weight of zinc, in particular at least 1% by weight of zinc, and up to 36% by weight of zinc, in particular up to 30% by weight of zinc, in particular up to 25% by weight of zinc, in particular up to 20% by weight of zinc, in particular up to 15% by weight of zinc. In particular, brass may be an α-brass containing up to 36% by weight of zinc. Bronze may be a bronze containing at least 0.5% by weight of tin, in particular at least 1% by weight of tin, and up to 20% by weight of tin, in particular up to 15% by weight of tin, in particular up to 10% by weight of tin, in particular up to 5% by weight of tin. The purity of the copper or the first copper alloy may be at least 93%, in particular at least 95%, in particular at least 99%, in particular at least 99.95%, and at most 99.99%.
[0028] The thickness of the metal foil can be at least 5 μm, in particular at least 10 μm, in particular at least 25 μm, in particular at least 50 μm, and in particular at most 200 μm, in particular at most 150 μm, in particular at most 100 μm, in particular at most 75 μm. In the case of large-area bonding, for example at 1000 mm 2 A bond line thickness of more than 100 μm is generally desired if the application is to be exposed to high thermomechanical stresses during its service life. One reason for this desire is that such a thickness can compensate for the relatively high warpage present in the surfaces of the first solid substrate and the second solid substrate to be connected, as well as the relatively high non-uniformity on these surfaces. The first solid substrate can be, for example, an electronic component and / or the second solid substrate can be a backplane. In addition, a bond line thickness of more than 100 μm has a good ability to handle high thermomechanical stresses between the first substrate and the second substrate.
[0029] The inventors of the present invention have found that if the metal foil has a relatively high thickness (particularly a thickness of at least 80 μm, 90 μm or 100 μm) and the composition is coated on the first surface and / or the second surface with a relatively low thickness (particularly a thickness of less than 10 μm), a bond line thickness of more than 100 μm can be provided.
[0030] Alternatively, the thermomechanical fatigue resistance may be adjusted by varying the porosity of the sintered composition and / or the additional composition coated on the first surface and / or the second surface of the metal foil.
[0031] The porosity of the sintered composition and / or the additional composition can be changed by changing the sintering parameters alone or in combination. For example, if the sintering is carried out for 3 minutes instead of 5 minutes, the porosity will generally be higher. Similarly, if only 1 MPa pressure is applied during the sintering process instead of 20 MPa, the porosity will be higher. Moreover, if the sintering is carried out at 250° C. instead of 300° C., the porosity will be higher.
[0032] In addition to or independently of the variation of porosity in the sintering composition and / or the additional composition, the metal foil and the thickness of the metal foil can be selected to have the desired strength. Therefore, depending on the design and application requirements, the two strategies can be used in combination or separately. The state-of-the-art technology for large-area interconnects described above uses printed solder paste or sintering paste with a thickness of 150μm-400μm, thus requiring relatively long pre-drying times and also generating voids after soldering / sintering.
[0033] Compared to relatively thick solder pastes or sintering pastes used in the art, such a coated metal foil shows good sinterability and enables a relatively fast sintering process with a relatively low amount of organic binder compared to a bond line of the same thickness provided by using only a sintering paste. The amount of organic binder can be reduced even more when the coated metal foil is pre-dried before the sintering process. A small amount of organic binder results in a uniform intermediate layer with few or even no unwanted irregular cavities in the intermediate layer. This is particularly advantageous in the case of large-area bonding, where a bonding thickness of at least 100 μm is desired and where a relatively large amount of organic binder typically results in the formation of a relatively large number of unwanted irregular cavities and voids. Such cavities and voids result in reduced reliability, thermal conductivity and electrical conductivity of the intermediate layer during operation and in the generation of local hot spots.
[0034] The metal foil, in particular the copper metal foil, may be a single crystal metal foil or a polycrystalline metal foil. The first surface and / or the second surface of the metal foil may be completely or partially oriented in a single crystal orientation, in particular a 111 crystal orientation, or may have a completely or partially disordered crystal structure.
[0035] The metal foil can be purchased, for example, as high tensile strength alloy copper foil (eg HTA-520, HTA-600, HTA-750), extra smooth copper foil or wrapped copper foil / flat copper foil, all of which are offered by Schlenk Metallfolien GmbH & Co. KG.
[0036] The lamella and / or the further lamella are formed of copper or a first copper alloy or a second copper alloy. The first copper alloy or the second copper alloy may be bronze or brass. If the lamella and / or the further lamella are formed of a first copper alloy or a second copper alloy instead of copper, the coated metal foil according to the invention can still have good thermal conductivity, in particular if the first copper alloy or the second copper alloy is bronze or brass. When the lamella is formed of copper, a higher thermal conductivity of the coated metal foil according to the invention can be obtained. The brass may be a brass containing at least 0.5% by weight of zinc, in particular at least 1% by weight of zinc, and at most 36% by weight of zinc, in particular at most 30% by weight of zinc, in particular at most 25% by weight of zinc, in particular at most 20% by weight of zinc, in particular at most 15% by weight of zinc. In particular, the brass may be an alpha-brass containing at most 36% by weight of zinc. In particular, the bronze may be a bronze containing at least 0.5 wt. % tin, in particular at least 1 wt. % tin, and at most 20 wt. % tin, in particular at most 15 wt. % tin, in particular at most 10 wt. % tin, in particular at most 5 wt. % tin. The purity of the copper or the first copper alloy or the second copper alloy may be at least 93%, in particular at least 95%, in particular at least 99%, in particular at least 99.95%, and at most 99.99%.
[0037] The flakes and / or further flakes may have an average particle size D50 determined by laser particle size analysis of at least 1 μm, in particular at least 2 μm, in particular at least 2.5 μm, in particular at least 3 μm, and at most 10 μm, in particular at most 7 μm, in particular at most 5 μm, in particular at most 4 μm, in particular at most 3.4 μm. The laser particle size analysis can be carried out using laser diffraction measurement according to the specification of ISO 13320 "Particle size analysis - laser diffraction method". The laser diffraction measurement can be carried out by Helos from Sympatec GmbH, 38678 Clausthal Zellerfeld, Germany. TM Laser diffractometer is used. The average particle size D50 is the corresponding particle size when the cumulative percentage reaches 50%. For example, for a powder sample with D50=50μm, it means that 50% of the particles are larger than 50μm and 50% of the particles are smaller than 50μm.
[0038] The flakes, in particular the copper flakes, may be single crystalline flakes or polycrystalline flakes. The copper flakes may be fully or partially oriented in a single crystal orientation, in particular in a 111 crystal orientation, or may have a fully or partially disordered crystal structure.
[0039] The flakes can be obtained by grinding in a ball mill and can have a thin layer shape, an irregular shape or a corn flake shape. The inventors of the present invention have found that compared with spherical particles, thin layer shapes, irregular shapes or corn flake shapes, especially thin layers with an average particle size D50 of at most 5 μm, especially an average particle size of at most 4 μm, especially an average particle size of at most 3.4 μm, especially an average particle size of at most 3 μm, will produce a better contact surface because even when a low bonding force (e.g., a bonding force of less than 1 MPa) is applied, the flakes can be closely stacked with each other. The thin layer shape, irregular shape or corn flake shape of the flakes, together with the relatively low thickness of the flakes, also leads to a relatively large surface area of the flakes, which leads to improved densification and roughening of the flakes during sintering. This further promotes the formation of sintering necks and allows material transport during sintering. Any of the flakes may independently of one another have a thickness in the range of 5 nm to 400 nm, in particular in the range of 20 nm to 350 nm, in particular in the range of 50 nm to 300 nm, in particular in the range of 100 nm to 275 nm, in particular in the range of 150 nm to 250 nm, in particular in the range of 175 nm to 200 nm.
[0040] The thin sheet and / or another thin sheet contain internal pores. The internal pores are defined as void spaces in the thin sheet or another thin sheet, which are not filled by the copper or the first copper alloy or the second copper alloy forming the thin sheet. Any internal pore exists in the grains of the copper or the first copper alloy or the second copper alloy forming the thin sheet and / or another thin sheet. The diameter of any internal pore can be in the range of 2nm to 30nm, particularly in the range of 3nm to 25nm, particularly in the range of 5nm to 20nm, particularly in the range of 10nm to 15nm. The diameter of the internal pore can be measured by image-based analysis of, for example, transmission electron microscopy (TEM) or scanning electron microscopy (SEM) images. The inventors of the present invention have found that, unlike the pores between grains, the internal pores do not shrink during the sintering process, thereby allowing relatively high stress absorption, particularly relatively high thermomechanical and / or mechanical stress absorption, in the case of temperature and / or pressure changes applied to the intermediate layer formed by the coated metal foil. This stress absorption of the internal pores of the thin sheet or another thin sheet obtains a relatively high resistance to thermomechanical fatigue, so that the intermediate layer formed by the coated metal foil has good thermomechanical properties. The internal pores also limit the crack propagation of the intermediate layer during the service life of operation. In the context of the present invention, thermomechanical stress refers to the stress generated in the intermediate layer due to the mismatch of thermal expansion coefficients, that is, the different expansion and contraction of the first and second solid substrates and the intermediate layer caused by thermal effects during and after sintering and / or during the operation of the device containing the intermediate layer between the first and second solid substrates. The inventors have found that the composition of the metal foil with a coating containing a thin sheet and / or another thin sheet with internal pores is particularly advantageous for the high thermomechanical stress absorption of the intermediate layer formed between the first solid substrate and the second solid substrate, especially if the first surface and the second surface of the foil are coated. The reason for this is that, in addition to the thin sheet or another thin sheet with internal pores, the metal foil as an interconnect / intermediate layer provides very good resistance to thermomechanical fatigue. This is further enhanced by the fact that the composition on the first surface of the foil and the further composition on the second surface may be different, allowing precise tuning according to the design specifications, requirements and coefficient of thermal expansion (CTE) of the first and second solid substrates.
[0041] In addition, the inventors of the present invention have found that mechanical stresses applied to the intermediate layer are also effectively absorbed by the intermediate layer produced by the coated metal foil according to the present invention, which contains thin sheets and / or additional thin sheets, and the thin sheets and / or additional thin sheets contain internal pores, compared to the intermediate layer obtained with copper sheets or copper alloy sheets without internal pores. Compared with the intermediate produced by the coated metal foil of copper or copper alloy containing copper sheets or copper alloy sheets without internal pores, the intermediate layer produced after sintering of the coated metal foil according to the present invention shows improved resistance to thermomechanical fatigue. In the context of the present invention, thermomechanical fatigue refers to the stacking of cyclic mechanical loads and cyclic thermal loads that cause material fatigue. Therefore, the intermediate layer produced by the coated metal foil according to the present invention shows good thermomechanical properties, especially if relatively high thermomechanical stresses and / or relatively high mechanical stresses are applied to the intermediate layer, thereby ensuring good reliability.
[0042] The average intragranular pore density of the thin sheet of copper, the first copper alloy or the second copper alloy or the further thin sheet may be 2 internal pores / μm 2 Up to 40 internal pores / μm 2 In the range of 2 internal pores / μm 2 Up to 30 internal pores / μm 2 In the range of 3 internal pores / μm 2 Up to 25 internal pores / μm 2 In the range of 5 internal pores / μm 2 Up to 20 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 18 internal pores / μm 2 In the range of 10 internal pores / μm 2 Up to 15 internal pores / μm 2 In the range of 12 internal pores / μm 2 Up to 13 internal pores / μm 2 The internal pores are present in any part, in particular in any arbitrary part, through any sheet or further sheet. In one embodiment, the average intragranular pore density of the sheet and / or further sheet, in particular only the copper sheet, the first copper alloy sheet or the second copper alloy sheet, is 7 internal pores / μm. 2 Up to 40 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 30 internal pores / μm 2In the context of the present invention, the average intra-grain pore density of a sheet or further sheet is defined as the average value of the number of internal pores relative to the area passing through any part of the sheet or further sheet. The inventors of the present invention have found that the average intra-grain pore density of the sheet and / or further sheet in the composition and / or further composition specified according to the present invention is not affected by the sintering of the coated metal foil according to the present invention. Therefore, the average intra-grain pore density of the sintered sheet and / or further sheet in the copper-containing intermediate layer / interconnect layer between two solid substrates can also be within 2 internal pores / μm 2 Up to 40 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 40 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 30 internal pores / μm 2 In the range of 2 internal pores / μm 2 Up to 30 internal pores / μm 2 In the range of 3 internal pores / μm 2 Up to 25 internal pores / μm 2 In the range of 5 internal pores / μm 2 Up to 20 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 18 internal pores / μm 2 In the range of 10 internal pores / μm 2 Up to 15 internal pores / μm 2 In the range, especially 12 internal pores / μm 2 Up to 13 internal pores / μm 2 In the range of , the internal pores penetrate the intermediate layer / interconnect layer in any part, in particular in any arbitrary part. Although the individual grain particles or flakes and / or further flakes are sintered together in the intermediate layer / interconnect layer so that no individual grains / flakes / further flakes exist in the intermediate layer / interconnect layer, the term "intra-grain pore density" remains unchanged because the origin of the pores is in the grains / flakes / further flakes. The average intra-grain pore density of the flakes / further flakes can be measured, for example, by gravimetric analysis, computer tomography analysis or image-based analysis. The average intra-grain pore density of the flakes / further flakes can be determined, for example, using the following method:
[0043] 1. embedding the sheet / other sheets in a resin, especially an epoxy resin,
[0044] 2. Preparation of ultrathin sections of embedded slices / additional slices,
[0045] 3. taking transmission electron microscope (TEM) images and / or scanning electron microscope (SEM) images of ultrathin sections of the embedded thin slice / additional thin slice,
[0046] 4. determining a plurality of intragranular pore densities by counting the number of internal pores in ultrathin sections of the flake / further flakes in a plurality of transmission electron microscopy (TEM) images and / or a plurality of scanning electron microscopy (SEM) images relative to the total area of these ultrathin sections of the flake / further flakes, and
[0047] 5. Calculate the average value of the multiple intra-particle pore densities determined in this way.
[0048] In this regard, step 4 may be achieved by computer-assisted image analysis of the TEM images and / or SEM images.
[0049] The inventors of the present invention have found that the average intra-grain pore density of a metal foil coated with the composition and / or another composition (the composition and / or another composition comprising copper, a thin sheet of the first copper alloy or the second copper alloy and / or another thin sheet) is between 2 internal pores / μm 2 Up to 40 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 40 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 30 internal pores / μm 2 In the range of 2 internal pores / μm 2 Up to 30 internal pores / μm 2 In the range of 5 internal pores / μm 2 Up to 20 internal pores / μm 2 The above characteristics increase the thermomechanical fatigue resistance of the intermediate layer of the present application in the range of 2 to 400 nm compared to the intermediate layer obtained from a copper metal foil or a copper alloy metal foil coated with a composition comprising a copper flake or a copper alloy flake without internal pores. In addition, the thermal conductivity and electrical conductivity of the intermediate layer obtained from the metal foil coated with the composition comprising flakes and / or another flake and / or another composition are not affected by the internal pores, and the average intragranular pore density of the flakes and / or another flakes is 2 internal pores / μm 2 Up to 40 internal pores / μm 2 In the range of 2 internal pores / μm 2 Up to 30 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 30 internal pores / μm 2 or 5 internal pores / μm 2 Up to 20 internal pores / μm 2It is the same or almost the same as the intermediate layer obtained by coating a metal foil with a composition comprising a copper flake or a copper alloy flake without internal pores. Therefore, since the average intragranular pore density of the flake / further flake is between 2 internal pores / μm 2 Up to 40 internal pores / μm 2 In the range of 2 internal pores / μm 2 Up to 30 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 30 internal pores / μm 2 or 5 internal pores / μm 2 Up to 20 internal pores / μm 2 The range of 200 μm ensures that the obtained intermediate layer has relatively high thermomechanical properties, relatively high thermal conductivity and relatively high electrical conductivity. The average intragranular pore density of the flakes / further flakes is 2 internal pores / μm 2 Up to 40 internal pores / μm 2 In the range of 2 internal pores / μm 2 Up to 30 internal pores / μm 2 In the range of 7 internal pores / μm 2 Up to 30 internal pores / μm 2 or 5 internal pores / μm 2 Up to 20 internal pores / μm 2 The resulting relatively high thermomechanical properties allow the intermediate layer / interconnect layer to be cooled quickly from the sintering temperature to the cooling temperature within a short period of time without causing excessive stresses in the intermediate layer, for example without fractures forming in the intermediate layer.
[0050] In contrast to the average intragranular pore density, in the context of the present invention, the average intergranular cavity density is defined as the average percentage of the area between the sintered flakes / additional flakes to the total cross-sectional area of the intermediate layer formed by the composition or additional composition specified in the present invention. The areas between the sintered flakes / additional flakes are not filled with metal. The average intergranular cavity density of the flakes / additional flakes in the intermediate layer (especially at the beginning of the sintering of the flakes / additional flakes) can be in the range of 5% to 50%, especially in the range of 10% to 45%, especially in the range of 15% to 40%, especially in the range of 20% to 35%, especially in the range of 25% to 30%. The average intergranular cavity density of the flakes / additional flakes in the intermediate layer can be measured by, for example, scanning electron microscopy (SEM) analysis, computer tomography analysis or image-based analysis of a cross section of the intermediate layer. In this regard, the cross section of the intermediate layer can be prepared by ion beam milling to avoid fouling or blocking of internal pores and / or intergranular cavities. The average interparticle void density of the flakes / further flakes in the intermediate layer can be determined, for example, using the following method:
[0051] 1. Prepare ultra-thin sections of the middle layer,
[0052] 2. Take SEM images of these ultra-thin sections,
[0053] 3. Determine multiple intergranular cavity densities by calculating the area between unfilled metal flakes / additional flakes in ultrathin sections of the intermediate layer in multiple SEM images relative to the total area of these ultrathin sections, and
[0054] 4. Calculate the average value of the multiple interparticle cavity densities determined in this way.
[0055] In this regard, step 3 can be achieved by computer-assisted image analysis of the SEM images.
[0056] The inventors of the present invention have found that, although the average intragranular pore density of the flakes / further flakes is not affected during the sintering of the coated metal foil according to the present invention, the average intergranular void density of the flakes / further flakes in the coated composition or further composition specified according to the present invention is reduced during the sintering of the coated metal foil according to the present invention. In this regard, the reduction in the average intergranular void density depends on the sintering time, the pressure applied during the sintering process and the sintering temperature. The pressure applied during the sintering of the coated metal foil between the first solid substrate and the second solid substrate is typically a bonding pressure applied to press the first substrate and the second substrate against each other. Relatively long sintering times, relatively high pressures and / or relatively high sintering temperatures applied during the sintering process lead to a relatively large reduction in the average intergranular void density. After sintering of the coated metal foil according to the invention, the average intergranular void density in the copper-containing intermediate layer / interconnect layer (especially between the sintered flakes / further flakes in the copper-containing intermediate layer / interconnect layer) may be in the range of 0.5% to 45%, especially in the range of 1% to 45%, especially in the range of 5% to 40%, especially in the range of 10% to 35%, especially in the range of 15% to 30%, especially in the range of 20% to 25%. During the sintering of the coated metal foil according to the invention, the reduction in the average intergranular void density may result in the complete or almost complete disappearance of the intergranular pores in the copper-containing intermediate layer / interconnect layer, especially between the sintered flakes / further flakes of the copper-containing intermediate / interconnect layer.
[0057] The thin sheets / further thin sheets are stacked in a uniform stacking pattern, in particular stacked horizontally on each other. Thus, a relatively large surface contact is provided between the thin sheets / further thin sheets. The relatively large surface contact between the thin sheets / further thin sheets allows sintering in a relatively short sintering time, at a relatively low sintering pressure and / or at a relatively low sintering temperature. In addition, the thin sheets / further thin sheets show a relatively high surface energy. Surface energy can be defined as the excess energy at the surface of a material compared to the bulk of the material.
[0058] The foil / additional foils can be purchased, for example, as Cubrotec 8000 copper foil or Cubrotec 8001 copper foil, both available from Carl Schlenk SE, Germany.
[0059] The flakes and / or further flakes may have a multilayer laminar structure, i.e. a structure in which a plurality of smaller flakes forming a thin layer are loosely stacked on top of each other but held together by van der Waals forces. The total thickness of the structure is preferably not more than 200 nm. The inventors of the present invention have found that, compared with copper flakes or copper alloy flakes without a laminar structure (especially without a multilayer laminar structure), the flakes of copper or copper alloy and / or further copper flakes with a multilayer laminar structure ensure that sintering is carried out in a relatively short sintering time (especially within a sintering time of at most 5 minutes) at a relatively low sintering temperature (especially a sintering temperature of at most 250° C.) and / or a relatively low sintering pressure (especially a sintering pressure of at most 15 MPa). This is achieved by the relatively large surface area of the flakes and / or further flakes with a multilayer laminar structure, which leads to an increase in the densification and rapid grain growth of the flakes and / or further flakes in the composition and / or further composition during sintering. The multilayered laminar structure of the lamella or further lamellae can be determined by surface analysis, in particular metal surface analysis, including the above-mentioned methods, and / or by analyzing a cross section of the lamella or further lamellae. The cross-sectional analysis can be performed, for example, by scanning electron microscopy (SEM), scanning tunneling microscopy (STM), transmission electron microscopy (TEM), glow discharge spectroscopy and image-based inspection of metal surfaces. These methods can also be applied to analyze a cross section of a copper-containing intermediate layer before and / or after sintering, a cross section of a coated metal foil according to the invention, a cross section of a metal foil specified according to the invention and / or a cross section of a composition or further composition, respectively.
[0060] The multilayer laminar structure may comprise or consist of at least 2, in particular at least 3, in particular at least 4, in particular at least 5, in particular at least 6, in particular at least 7, in particular at least 8, and at most 20, in particular at most 18, in particular at most 16, in particular at most 14, in particular at most 12, in particular at most 11, in particular at most 10, in particular at most 9 thin layers. The thickness of any one thin layer may be independently of one another in the range of 5nm to 20nm, in particular in the range of 6nm to 18nm, in particular in the range of 8nm to 16nm, in particular in the range of 10nm to 14nm, in particular in the range of 11nm to 13nm. By analyzing the cross section of the thin slice / other thin slice, the number of thin layers in the multilayer laminar structure and / or the thickness of any thin layer in the multilayer laminar structure can be determined. For example, cross-sectional analysis can be performed by SEM or TEM of the cross section of the thin slice / other thin slice. The number of thin layers in the multilayer laminar structure of the thin slice / other thin slice can be determined, for example, by using the following method:
[0061] 1. embedding the sheet / other sheets in a resin, especially an epoxy resin,
[0062] 2. Preparation of ultrathin sections of embedded slices / additional slices,
[0063] 3. taking transmission electron microscope (TEM) images and / or scanning electron microscope (SEM) images of ultrathin sections of the embedded lamella / additional lamella, and
[0064] 4. Counting the number of lamellae in the multilayered laminar structure within the lamellae / ultrathin sections of the additional lamellae in the TEM images and / or SEM images.
[0065] In this regard, step 4 may be achieved by computer-assisted image analysis of the TEM images and / or SEM images.
[0066] The multilayer laminar structure can extend over the entire lamella or a portion of the lamella. The total thickness of the multilayer laminar structure can be at least 20 nm, particularly at least 50 nm, particularly at least 100 nm, and at most 400 nm, particularly at most 350 nm, particularly at most 300 nm, particularly at most 250 nm, particularly at most 200 nm.
[0067] The copper or copper alloy forming the thin layer may have a nanocrystalline structure comprising or consisting of nanoscale grains. The copper or copper alloy forming the thin layer may be the same as the copper or copper alloy forming the thin slice / other thin slice. The size of the nanoscale grains may be in the range of 5nm to 200nm, in particular in the range of 5nm to 100nm, in particular in the range of 10nm to 90nm, in particular in the range of 15nm to 80nm, in particular in the range of 20nm to 70nm, in particular in the range of 25nm to 60nm, in particular in the range of 30nm to 50nm, in particular in the range of 35nm to 40nm. If the metal forming the thin layer (i.e. copper or the first copper alloy or the second copper alloy) has a nanocrystalline structure comprising or consisting of nanoscale grains, rapid grain growth of the thin slice / other thin slice can be ensured during the sintering process. In this regard, in the later stages of sintering, when the density of intergranular cavities decreases, the intergranular pores of the thin slices / other thin slices in the copper-containing intermediate layer / interconnection layer disappear completely or almost completely, and the intragranular pores remain, the rapid growth of grains is particularly significant. In those later stages of sintering, if the metal forming the thin layer has a nanocrystalline structure comprising or consisting of nanoscale grains, then this point that grain boundary migration becomes the main process mechanism of grain growth is particularly significant. Therefore, if the metal forming the thin layer has a nanocrystalline structure comprising or consisting of nanoscale grains, it is conducive to sintering with a relatively low sintering pressure and / or with a relatively low sintering temperature in a relatively short sintering time. The grain structure can be detected and analyzed, for example, by the following: the thin slice / other thin slice is analyzed using an electron backscatter diffraction technique (EBSD).
[0068] In a multilayer laminar structure, each lamina may be in contact with (one) another / multiple laminas via at least one laminar boundary. Furthermore, a lamina may be part of a layer that is bent around the edge of the lamina. This means that the lamina forms a unit in the form of a lamina with a multilayer laminar structure.
[0069] Thin slice and / or other thin slice can be coated with stearic acid. In each case, the total weight of stearic acid relative to the total weight of the thin slice coated with stearic acid and / or the total weight of stearic acid relative to the total weight of other thin slice coated with stearic acid can be independently of each other at least 0.001 weight %, particularly at least 0.005 weight %, particularly at least 0.01 weight %, particularly at least 0.05 weight %, particularly at least 0.075 weight %, and at most 1.5 weight %, particularly at most 1.25 weight %, particularly at most 1 weight %, particularly at most 0.75 weight %, particularly at most 0.5 weight %, particularly at most 0.25 weight %, particularly at most 0.1 weight %. In particular, in each case, the total weight of stearic acid relative to the total weight of the thin slice coated with stearic acid and / or the total weight of stearic acid relative to the total weight of other thin slice coated with stearic acid can be independently of each other at most 1.5 weight %. The inventors of the present invention have found that stearic acid coated on the surface of a thin sheet or another thin sheet prevents agglomeration and cold welding of the thin sheet or another thin sheet. However, due to the boiling point of 361°C, the stearic acid on the surface of the thin sheet or another thin sheet will not completely evaporate during the sintering process at a relatively low temperature and a relatively short sintering duration. Copper-containing particles coated with an organic coating agent (especially stearic acid) generally show a relatively low sintering efficiency. The inventors of the present invention have found that the relatively low sintering efficiency only occurs when the thin sheet and / or another thin sheet included in the coated metal foil is coated with a relatively high total weight of stearic acid (relative to the total weight of the thin sheet and / or another thin sheet coated with stearic acid) (especially the total weight of stearic acid relative to the total weight of the thin sheet and / or another thin sheet coated with stearic acid is greater than 1.5 weight %).
[0070] In one embodiment, the total weight of stearic acid is at least 0.7% by weight and at most 1.5% by weight relative to the total weight of the copper or copper alloy flakes coated with stearic acid. It has been found that a total weight of 0.7% by weight of stearic acid relative to the total weight of the flakes is high enough to prevent the flakes from agglomerating and cold welding under all relevant ball milling conditions. It has been found that a total weight of 1.5% by weight of stearic acid relative to the total weight of the flakes is low enough to not hinder subsequent sintering. The inventors have found that a total weight above this value will hinder sintering because the flakes contain a high organic content and must leave the composition containing these flakes before surface diffusion can occur to ensure sintering. It has been found that 1.5% by weight of stearic acid relative to the total weight of the flakes is a limit beyond which the sintering results are unsatisfactory.
[0071] It has been found that a total weight of stearic acid of at least 0.001 wt.-%, in particular at least 0.005 wt.-%, in particular at least 0.01 wt.-%, in particular at least 0.05 wt.-%, in particular at least 0.075 wt.-%, relative to the total weight of the flakes, is sufficiently high to prevent agglomeration and cold welding of the flakes under many but not all relevant conditions.
[0072] The inventors of the present invention have found that a relatively low total weight of stearic acid, i.e. at most 1.5 wt. % stearic acid relative to the total weight of the flakes and / or further flakes coated with stearic acid in the composition or in another composition, is sufficient to prevent agglomeration and cold welding of the flakes and / or further flakes and also to improve or at least not hinder the sintering of these flakes. The inventors have also found that, compared to copper-coated metal foil or copper alloy-coated metal foil comprising copper or copper alloy flakes and / or further flakes coated with a higher total weight of stearic acid (especially at least 1.6 wt. % stearic acid, especially at least 2 wt. % stearic acid, especially at least 4 wt. % stearic acid, relative to the total weight of the flakes and / or further flakes coated with stearic acid), compositions and / or further compositions comprising flakes and / or further flakes coated with a relatively low total weight of stearic acid (i.e., at most 1.5 wt. % stearic acid, relative to the total weight of the flakes and / or further flakes coated with stearic acid), show improved particle contact during the sintering process of the coated metal foil. Therefore, a coated metal foil comprising flakes and / or further flakes coated with a relatively low total weight of stearic acid (i.e. up to 1.5 wt. % stearic acid) relative to the total weight of the flakes and / or further flakes coated with stearic acid ensures improved formation of sintering necks, thereby allowing sintering at short sintering times, low sintering temperatures and / or low sintering pressures.
[0073] Furthermore, compared to flakes without an organic coating (particularly flakes without a stearic acid coating), flakes and / or further flakes coated with a relatively low total weight of stearic acid (i.e. up to 1.5% by weight of stearic acid) relative to the total weight of the flakes and / or further flakes with stearic acid in the coated composition and / or further composition do not agglomerate, in particular during the process for forming the composition and / or further composition as provided in the invention (and if the composition is coated on the first surface and / or on the second surface of the metal foil and / or if the further composition is coated on the second surface) and / or during storage (and if the composition is coated on the first surface and / or on the second surface of the metal foil and / or if the further composition is coated on the second surface). Agglomeration impedes the formulation of the composition and / or further composition as a paste, since agglomeration forms relatively large lumps, which impede homogeneous mixing of the flakes or further flakes with the organic binder or further organic binder. The agglomeration of thin slice or other thin slice also causes the first surface and / or second surface of metal foil to be coated unevenly and inconsistently by composition or other composition, and also causes the adhesion of coated metal foil to the first substrate and / or second substrate to be insufficient. If composition is coated on the first surface and / or second surface of metal foil or if other composition is coated on the second surface of metal foil or the first surface and / or second surface of metal foil is heated to pre-drying temperature together with composition and / or other composition before sintering, then the above situation may especially occur. Pre-drying causes the evaporation of organic binder or other organic binder in composition or other composition specified according to the present invention, particularly partial evaporation, and causes the evaporation of optional polar organic solvent or optional turpentine in composition or other composition, particularly partial evaporation. This causes the thin slice or other thin slice to be obviously agglomerated in the case of the thin slice or other thin slice without organically coated copper, the first copper alloy or the second copper alloy. Thin slice or other thin slice obviously agglomerates and causes the composition or other composition to be unevenly distributed on the first surface and / or second surface of metal foil. In addition, due to the inhomogeneity caused by the agglomerated flakes or other flakes, the contact surface between the coated composition and the first surface and / or the second surface of the metal foil or between the coated other composition and the second surface of the metal foil is relatively small, which results in an uneven pressure distribution during the sintering process of the coated metal foil, thereby resulting in uneven sintering of the coated metal foil.
[0074] Thus, by preventing agglomeration of flakes and / or further flakes in the composition, uniform and consistent coating and / or applicability, in particular printability, is ensured, as well as sufficient adhesion of the composition on the first surface and / or second surface of the metal foil and / or sufficient adhesion of the further composition on the second surface of the metal foil, in particular if the composition on the first surface and / or second surface of the metal foil and / or the further composition on the second surface of the metal foil or the first surface and / or second surface together with the composition and / or the further composition are heated to a pre-drying temperature before sintering. This is particularly important when the composition is applied to the first surface and / or second surface of the metal foil at a relatively low thickness (e.g. less than 20 μm) and / or the further composition is applied to the second surface of the metal foil at a relatively low thickness (e.g. less than 20 μm). Thus, after sintering, the coated metal foil ensures sufficient copper bonding between the first substrate and the second substrate with relatively high arithmetic mean shear strength values, in particular if the coated metal foil comprises flakes and / or further flakes coated with stearic acid in a relatively low total weight, i.e. at most 1.5 wt. % of stearic acid relative to the total weight of the flakes and / or further flakes coated with stearic acid. In addition, coated metal foils comprising copper flakes or copper alloy flakes coated thereon with a higher total weight of stearic acid, in particular at least 1.6 wt. % of stearic acid, in particular at least 2 wt. % of stearic acid, in particular at least 4 wt. % of stearic acid, lead to stearic acid residues remaining after sintering. A higher total weight of stearic acid also results in the adhesion of the organic binder to the first and / or second surface of the metal foil and / or the adhesion of the additional organic binder to the second surface of the metal foil being stronger than the cohesion of the organic binder and / or the additional organic binder in the composition and / or the additional composition, resulting in an effect generally referred to as bleed-out. If the composition is applied to the first and / or second surface of the metal foil and / or the additional composition is applied to the second surface of the metal foil, the bleed-out of the organic binder or the additional organic binder results in the organic binder or the additional organic binder being unevenly distributed on the first and / or second surface of the metal foil, and flakes and / or additional flakes being entrained due to the uneven distribution of the organic binder and / or the additional organic binder on the first and / or second surface of the metal foil. Thus, the composition or further composition according to the invention comprising flakes or further flakes coated with a relatively low total weight of stearic acid (relative to the total weight of the flakes or further flakes coated with stearic acid) shows improved processing properties and improved sintering efficiency compared to compositions comprising copper flakes or copper alloy flakes without an organic coating and compared to compositions comprising flakes of copper or copper alloy coated with a relatively high total weight of stearic acid (relative to the total weight of the flakes coated with stearic acid, in particular at least 2% by weight of stearic acid).
[0075] The inventors of the present invention have found that after the sintering process, the sintered flakes and / or further flakes are evenly distributed in the copper-containing intermediate layer, in particular between the first surface of the metal foil and the first solid substrate and between the second surface of the metal foil and the second solid substrate. This allows for efficient formulation of the composition and / or further composition specified according to the invention, improved coating and / or applicability, in particular the printability of the composition and / or further composition according to the invention on the first surface and / or the second surface of the metal foil. In addition, the coated metal foil according to the present invention ensures relatively good surface control of the sintered copper-containing intermediate layer by ensuring a relatively low surface roughness and a uniform bond thickness of the copper-containing intermediate layer, in particular during and / or after sintering. Furthermore, if the flakes and / or further flakes are coated with a relatively low total weight of stearic acid, i.e. up to 1.5 wt. % stearic acid relative to the total weight of the flakes and / or further flakes coated with stearic acid, agglomeration of the flakes and / or further flakes is prevented, thereby further improving the uniform distribution of the flakes and / or further flakes in the copper-containing intermediate layer after the sintering process, in particular between the first surface of the metal foil and the first solid substrate and between the second surface of the metal foil and the second solid substrate. This further improves the coating and / or applicability, in particular the printing properties, of the composition on the first surface and / or the second surface of the metal foil and / or the further combination on the second surface of the metal foil. Furthermore, if the flakes and / or further flakes are coated with a relatively low total weight of stearic acid, i.e. at most 1.5 wt. % stearic acid relative to the total weight of the flakes and / or further flakes coated with stearic acid, surface control of the sintered copper-containing interlayer is further improved by ensuring a relatively low surface roughness and a uniform bond thickness of the copper-containing interlayer, in particular during and / or after sintering.
[0076] The inventors of the present invention have found that, in addition to the multi-layered structure of the flakes and / or additional flakes, the following properties of the flakes and / or additional flakes in the composition according to the present invention and / or additional composition also each contribute to ensuring sintering within a relatively short sintering time, at a relatively low sintering pressure and / or at a relatively low sintering temperature, as described above: a relatively large surface contact (this is due to the uniform stacking of the flakes in the composition according to the present invention and / or additional flakes in the additional composition according to the present invention and on the first surface and / or second surface of the metal foil), a thin layer of the flakes and / or additional flakes formed of metal having a nanocrystalline structure containing nanocrystals or consisting of nanocrystals, and a flake and / or additional flake coated with stearic acid having a relatively low total weight, i.e., at most 1.5% by weight of stearic acid (relative to the total weight of the flakes and / or additional flakes coated with stearic acid). The inventors of the present invention further found that compared with copper sheets or copper alloy sheets without a layered structure (especially without a multi-layered structure), or compared with copper sheets or copper alloy sheets that only have a multi-layered structure but do not satisfy any of the above-mentioned properties, or compared with copper sheets or copper alloy sheets that have a multi-layered structure but do not satisfy all of the above-mentioned properties, if the sheet and / or another sheet not only has a multi-layered structure but also satisfies two of the above-mentioned properties or even three of the above-mentioned properties, the multi-layered structure of the sheet and / or another sheet and each of the above-mentioned properties reinforce each other, thereby producing a synergistic effect, and thus allowing sintering at an even lower sintering pressure and / or an even lower sintering temperature in an even shorter sintering time.
[0077] The total oxygen content of the flakes and / or further flakes may be in the range of 3% to 8% by weight, in particular in the range of 4% to 7.9% by weight, in particular in the range of 4.1% to 7.5% by weight, in particular in the range of 4.2% to 7% by weight, in particular in the range of 4.3% to 6.5% by weight, in particular in the range of 4.4% to 6% by weight, in particular in the range of 4.5% to 5.5% by weight, in particular in the range of 4.6% to 5% by weight. In the context of the present invention, the total oxygen content of the flakes and / or further flakes refers to oxygen atoms in any form, for example in the form of copper oxide on the surface of the flakes and / or further flakes, as well as the oxygen content of the flakes and / or further flakes themselves, for example originating from oxygen trapped in internal pores or in the lamellar structure. If the flakes and / or further flakes are coated with stearic acid, the total oxygen content also refers to the oxygen content of the stearic acid coating of the flakes / further flakes.
[0078] The organic binder and / or the further organic binder may be a liquid organic binder. The organic binder and / or the further organic binder may be, independently of one another, terpineol, a primary alcohol, a diol, a triol, a polymeric diol, or a mixture of at least two of terpineol, a primary alcohol, a diol, a triol and a polymeric diol. In particular, the terpineol forming the organic binder or the further organic binder may be α-terpineol. α-terpineol may be (R)-(+)-α-terpineol, (S)-(–)-α-terpineol or a mixture of (R)-(+)-α-terpineol and (S)-(–)-α-terpineol. (R)-(+)-α-terpineol and / or (S)-(–)-α-terpineol may each independently have a purity of at least 90%, in particular at least 93%. The primary alcohol forming the organic binder may be 1-butanol or 1-octanol. The diol forming the organic binder or the further organic binder may be a diol having an average molar mass of at least 60 g / mol and at most 110 g / mol, in particular ethylene glycol, diethylene glycol, propylene glycol or butanediol. The triol forming the organic binder or the further organic binder may be a triol having an average molar mass of at least 75 g / mol and at most 110 g / mol, in particular glycerol. The polymeric diol forming the organic binder or the further organic binder may be a polymeric diol having an average molar mass of at least 200 g / mol, in particular at least 300 g / mol, in particular at least 400 g / mol, in particular at least 500 g / mol, in particular at least 550 g / mol, and at most 800 g / mol, in particular at most 750 g / mol, in particular at most 700 g / mol, in particular at most 650 g / mol.
[0079] During the sintering process, the organic binder and / or the additional organic binder, in particular the residual organic binder and / or the residual additional organic binder, usually evaporate or decompose. During the evaporation or decomposition of the diol and / or the polymeric diol, a reducing atmosphere is generated, which prevents the copper coated on the metal foil from being oxidized to copper oxide without the need to provide an additional protective gas atmosphere applied from the outside. Therefore, the diol and / or the polymeric diol in the composition or the additional composition specified according to the invention ensures that the Cu oxide is reduced in situ without any difficulty during the sintering process. During the sintering process, the in situ reduction of the copper oxide (in particular Cu2O) also leads to the formation of copper nanoparticles, which further contribute to the sintering due to their high surface area and reactivity. The organic binder or the additional organic binder, in particular the polymeric diol, in particular the polymeric diol with an average molar mass of at least 550 g / mol and at most 650 g / mol, has a reducing effect on the coated metal foil.
[0080] Compared to polymeric diols, in particular polyethylene glycol, in particular polyethylene glycol having an average molar mass of more than 200 g / mol, the evaporation of diols, in particular diols having an average molar mass of at least 60 g / mol and at most 110 g / mol, and the evaporation of primary alcohols, in particular 1-butanol and 1-octanol, is achieved at relatively low temperatures, in particular at temperatures of up to 200° C. For example, the evaporation of ethylene glycol is achieved at a temperature of 197° C. For example, the evaporation of 1-butanol is achieved at a temperature of 117.7° C. For example, the evaporation of 1-octanol is achieved at a temperature of 195° C. For evaporating polyethylene glycol, relatively high temperatures of at least 200° C. are required. However, the evaporation of the organic binder or further organic binder at relatively high temperatures results in the need for relatively high sintering temperatures or relatively long sintering times at relatively high sintering temperatures in order to ensure complete evaporation of the organic binder or further organic binder. Using a mixture of ethylene glycol and α-terpineol, it is also possible to achieve a combined effect of relatively low sintering temperature (eg, sintering temperature below 250° C.) and relatively fast sintering (eg, sintering in less than 5 minutes), while also utilizing a reducing atmosphere.
[0081] In one embodiment of the invention, the organic binder or other organic binder can be a mixture of ethylene glycol and alpha-terpineol. In another embodiment of the invention, the organic binder or other organic binder can be a mixture of alpha-terpineol, ethylene glycol and polyethylene glycol. In this mixture, the gross weight of alpha-terpineol can be 80 weight % relative to the gross weight of the organic binder or other organic binder, the gross weight of ethylene glycol can be 18 weight % relative to the total weight of the organic binder or other organic binder, and the gross weight of polyethylene glycol can be 2 weight % relative to the gross weight of the organic binder or other organic binder. In another embodiment of the invention, the organic binder or other organic binder can be a mixture of alpha-terpineol, polyethylene glycol and glycerol. In the mixture, the total weight of α-terpineol can be 80 weight % relative to the total weight of the organic binder or another organic binder, the total weight of polyethylene glycol can be 19.5 weight % relative to the total weight of the organic binder or another organic binder, and the total weight of glycerol can be 0.5 weight % relative to the total weight of the organic binder or another organic binder.
[0082] In another embodiment of the present invention, the organic binder or another organic binder can be a mixture of ethylene glycol, alpha-pinene alcohol, polyethylene glycol and glycerol. The inventors of the present invention have found that the mixture of alpha-pinene alcohol, ethylene glycol and polyethylene glycol, the mixture of alpha-pinene alcohol, polyethylene glycol and glycerol, and the mixture of ethylene glycol, alpha-pinene alcohol, polyethylene glycol and glycerol, the resulting composition allows relatively fast pre-drying without evaporating the composition specified according to the present invention. This results in the composition having a relatively high stability, particularly a relatively high stability of the composition after pre-drying, and a relatively long service life of the composition specified according to the present invention, particularly a relatively long service life of up to one week after pre-drying of the composition specified according to the present invention. In addition, even after the pre-drying of the coated metal foil, the composition specified according to the present invention also ensures full adhesion to the first surface and / or the second surface of the metal foil, and therefore, no additional tackifier (tacking agent) is required in the composition specified according to the present invention.
[0083] The composition and / or other composition specified according to the present invention may further contain a polar organic solvent or turpentine independently of each other. The polar organic solvent may be a liquid polar organic solution. Turpentine may be liquid turpentine. Both the polar organic solvent and turpentine may be used as a thinning agent. For the purposes of the present invention, a polar solvent is defined as a solvent having a dielectric constant of at least 7 measured at 20°C. A non-polar solvent is defined as a solvent having a dielectric constant of less than 7 at 20°C. Here, the dielectric constant of a given solvent is the ratio of the conductivity of the solvent to the conductivity of free space (i.e., vacuum). The dielectric constant may be measured by an LCR tester or an impedance analyzer by methods known in the art. The polar solvent may be, in particular, an alcohol, acetone, or a mixture of an alcohol and acetone. The alcohol may be methanol, ethanol, propanol, isopropanol, or a mixture of at least two of methanol, ethanol, propanol, and isopropanol. The inventors of the present invention have found that the composition or the further composition further comprising a polar organic solvent or turpentine ensures that the composition or the further composition is coated on the first surface and / or the second surface of the metal foil in each case independently of one another in a relatively low thickness, in particular a thickness of at most 10 μm, in particular a thickness of at most 5 μm, in particular a thickness of at most 1 μm.
[0084] The total content of solids in the composition or further composition specified according to the invention may be up to 80 wt %, in particular up to 75 wt %, in particular up to 70 wt %, in particular up to 65 wt %, in particular up to 63 wt %, in particular up to 60 wt %, in particular up to 55 wt %, in particular up to 50 wt %, in particular up to 40 wt %, in particular up to 30 wt %, in particular up to 20 wt %, in particular up to 10 wt %. Thus, compared to a silver sintering paste having a total solid content of about 90 wt %, the total solid content in the composition or further composition specified according to the invention is considerably lower. The relatively low total solid content results in a relatively low viscosity of the composition specified according to the invention. The viscosity of the composition specified according to the invention may be in the range of 50 mPas to 400.000 mPas, in particular in the range of 100 mPas to 350.000 mPas, in particular in the range of 200 mPas to 200.000 mPas. The viscosity of the composition or another composition according to the invention can be measured at room temperature (especially at 20° C.) using a standard viscometer (especially a standard classical rotational viscometer) (especially Thermo Scientific TM HAAKE TM Viscotester TM C) measurement. These rotational viscometers measure the resistance of the composition specified according to the invention or another composition relative to a preset speed. The torque or resistance generated is a measure of the viscosity of the composition specified according to the invention or another composition. The higher the torque, the higher the viscosity. The low viscosity of the composition specified according to the invention or another composition ensures that it is easy to process and has good and uniform spreadability on the first surface and / or second surface of the metal foil.
[0085] The total weight of the flakes or further flakes, optionally coated with stearic acid, relative to the total weight of the composition or further composition specified according to the invention can be up to 80% by weight, in particular up to 75% by weight, in particular up to 70% by weight, in particular up to 65% by weight, in particular up to 63% by weight, in particular up to 60% by weight, in particular up to 55% by weight, in particular up to 50% by weight, in particular up to 45% by weight, in particular up to 40% by weight, in particular up to 30% by weight, in particular up to 20% by weight, in particular up to 10% by weight. The remainder of the composition or further composition can be formed by the organic binder or further organic binder. This means that the total weight of the organic binder or further organic binder relative to the total weight of the composition or further composition specified according to the invention can be at least 20% by weight, in particular at least 25% by weight, in particular at least 30% by weight, in particular at least 35% by weight, in particular at least 37% by weight, in particular at least 40% by weight, in particular at least 45% by weight, in particular at least 50% by weight, in particular at least 55% by weight, in particular at least 60% by weight, in particular at least 70% by weight, in particular at least 80% by weight, in particular at least 90% by weight. If the composition or the further composition provided according to the invention further comprises a polar organic solvent or turpentine, the remainder of the composition or the further composition may be formed by the polar organic solvent or turpentine. The ratio of the total weight of the polar organic solvent to the total weight of the flakes together with the organic binder or to the total weight of the further flakes together with the organic binder or the further organic binder may be at most 10:1, in particular at most 5:1, in particular at most 4:1, in particular at most 3:1, in particular at most 2:1, in particular at most 1:1, in particular at most 1:2, in particular at most 1:3, in particular at most 1:4. The ratio of the total weight of turpentine to the total weight of flakes together with organic binder or to the total weight of further flakes together with organic binder or further organic binder may be at most 10:1, in particular at most 5:1, particularly at most 4:1, in particular at most 3:1, in particular at most 2:1, in particular at most 1:1, in particular at most 1:2, in particular at most 1:3, in particular at most 1:4. The inventors have found that a relatively high ratio of the total weight of polar organic solvent or turpentine to the total weight of flakes together with organic binder in the composition specified according to the invention or to the total weight of further flakes together with organic binder or further organic binder in the further composition specified according to the invention ensures that the composition or further composition is applied independently of one another in each case to the first and / or second surface of the metal foil in a relatively low thickness, in particular a thickness of at most 10 μm, in particular at most 5 μm, in particular at most 1 μm.The total weight of the flakes, further flakes, organic binders, further organic binders, optional stearic acid and / or optional polar organic solvent or optional turpentine applied on the flakes or further flakes can be determined by nuclear magnetic resonance spectroscopy, thermogravimetric analysis, mass spectrometry and infrared spectroscopy, respectively. The total weight of the flakes, further flakes, organic binders, further organic binders, optional stearic acid and / or optional polar organic solvent or optional turpentine applied on the flakes or further flakes can be determined by weighing the flakes, further flakes, organic binders, further organic binders, optional stearic acid and / or optional polar organic solvent or optional turpentine before forming the composition or further composition specified according to the invention.
[0086] An area of 10% to 100% (particularly 50% to 100%, particularly 55% to 95%, particularly 60% to 90%, particularly 65% to 85%, particularly 70% to 80%) of the total area of the first surface and / or the total area of the second surface of the metal foil can be coated independently of each other with the composition specified according to the invention. Optionally, an area of 10% to 100% (particularly 50% to 100%, particularly 100%) of the total area of the first surface of the metal foil can be coated with the composition, and an additional area of 10% to 100% (particularly 50% to 100%, particularly 100%) of the total area of the second surface of the metal foil can be coated with an additional composition. This area can be an area of 100% of the total area of the first surface and / or the total area of the second surface. The composition can be applied to the first surface (especially the area of the first surface) of the metal foil and / or to the second surface (especially the area of the second surface) of the metal foil, in each case independently of one another, with a thickness of at least 1 μm and at most 500 μm (in particular with a thickness of at least 1 μm and at most 50 μm, or with a thickness of at least 5 μm and at most 400 μm, in particular with a thickness of at least 10 μm and at most 300 μm, in particular with a thickness of at least 20 μm and at most 250 μm, in particular with a thickness of at least 50 μm and at most 200 μm, in particular with a thickness of at least 75 μm and at most 150 μm, in particular with a thickness of at least 100 μm and at most 125 μm). Optionally, the composition can be applied to the first surface of the metal foil, and the further composition can be applied to the second surface of the metal foil, in each case independently of one another, with a thickness of at least 1 μm and at most 500 μm (in particular with a thickness of at least 1 μm and at most 50 μm). If the composition or the further composition is applied in each case with a thickness of at least 1 μm and at most 50 μm, the sintered layer formed from the composition or the further composition can in each case have a thickness of at least 200 nm and at most 25 μm.
[0087] The coated metal foil can be arranged between the first solid substrate and the second solid substrate as a copper-containing intermediate layer connecting the first solid substrate to the second solid substrate, or arranged on the solid substrate for connecting the solid substrate to the metal foil. After the sintering process, electrical and / or thermal conduction can be formed between the solid substrate and the metal foil or between the first solid substrate and the metal foil through the composition coated on the metal foil. If the solid substrate is connected only to the metal foil, the metal foil can dissipate heat from the solid substrate and serve as a heat sink, or it can dissipate heat to another heat sink. The solid substrate connected only to the metal foil can also be a precursor of a conductor plate.
[0088] The method for forming a thin sheet or another thin sheet comprises the step of grinding and / or milling copper particles or copper alloy particles. If a thin sheet or another thin sheet coated with stearic acid is to be obtained, the copper particles or copper alloy particles are ground and / or milled in the presence of stearic acid. Grinding and / or milling can be carried out in, for example, a ball mill. Thin sheets or another thin sheets are obtained during the grinding and / or milling of copper particles or copper alloy particles. In the process of grinding and / or milling copper particles or copper alloy particles in the presence of stearic acid, a thin sheet or another thin sheet coated with stearic acid is obtained. In the process of grinding and / or milling copper particles or copper alloy particles in the presence of stearic acid, the total weight of stearic acid can be relatively low relative to the total weight of copper particles or copper alloy particles. In addition, in the presence of stearic acid, the total number of grinding and / or milling steps of copper particles or copper alloy particles alone can be relatively low. In particular, in the presence of stearic acid, the total number of grinding and / or milling steps of copper particles or copper alloy particles alone can be at most three, particularly at most two, particularly at most one, respectively. This ensures that a flake or further flake coated with stearic acid is obtained in which the total weight of stearic acid is at most 1.5 wt. % relative to the total weight of the flake or further flake coated with stearic acid. The total weight of stearic acid coated on the flake or further flake in relation to the total weight of the flake or further flake coated with stearic acid can be determined by nuclear magnetic resonance spectroscopy, thermogravimetric analysis, Rutherford backscattering spectroscopy, mass spectroscopy, infrared spectroscopy, Raman spectroscopy and X-ray spectroscopy in combination with nuclear magnetic resonance spectroscopy.
[0089] A method for forming a composition according to the invention, comprising the steps of providing an organic binder, a flake optionally coated with stearic acid and an optional polar organic solvent or an optional turpentine, and mixing the organic binder, the flake optionally coated with stearic acid and an optional polar organic solvent or an optional turpentine to obtain a composition according to the invention. A method for forming a further composition according to the invention, comprising the steps of providing an organic binder or a further organic binder, a flake optionally coated with stearic acid or an additional flake and an optional polar organic solvent or an optional turpentine, and mixing the organic binder or a further organic binder, a flake optionally coated with stearic acid or an additional flake and an optional polar organic solvent or an optional turpentine to obtain a further composition according to the invention. The further composition may differ from the composition not only in the individual components but also, in the case of identical components, in different weight ratios of the components to one another.
[0090] The invention also relates to a method for producing a coated metal foil according to the invention, comprising the following steps:
[0091] a) Provide:
[0092] - the copper metal foil or the first copper alloy metal foil or the copper metal foil plated with nickel-iron alloy as described above, wherein the metal foil has a first surface and a second surface,
[0093] - a sheet of copper or a first copper alloy or a second copper alloy as described above and optionally a further sheet of copper or a first copper alloy or a second copper alloy, wherein the sheet and the further sheet contain internal pores, and
[0094] - an organic binder as described above and optionally a further organic binder, and optionally a polar organic solvent as described above or optionally turpentine as described above,
[0095] b) mixing the flakes, the organic binder and optionally a polar organic solvent or optionally turpentine to obtain a composition, and optionally mixing the flakes or the further flakes and the organic binder or the further organic binder and optionally a polar organic solvent or optionally turpentine to obtain a further composition, and
[0096] c) applying the composition obtained in step b) to the first surface and / or the second surface of the metal foil, or applying the composition obtained in step b) to the first surface of the metal foil and applying the other composition obtained in step b) to the second surface of the metal foil to obtain the coated metal foil.
[0097] Therefore, the coated metal foil according to the present invention can be produced by the above-mentioned method. The composition obtained in step b) can be a composition specified according to the present invention, and the further composition obtained in step b) can be a further composition specified according to the present invention. In each case, applying the composition obtained in step b) to the first surface and / or the second surface of the metal foil, or applying the composition obtained in step b) to the first surface of the metal foil and applying the further composition obtained in step b) to the second surface of the metal foil can be carried out by coating, in particular blade coating or spraying, by dipping, by printing, in particular stencil printing, inkjet printing, aerosol jet printing or screen printing, by direct writing or by material dispensing.
[0098] The composition and / or the further composition may be applied independently of one another to 10% to 100%, in particular 50% to 100%, in particular 55% to 95%, in particular 60% to 90%, in particular 65% to 85%, in particular 70% to 80% of the area of the first surface and / or the area of the second surface of the metal foil. This area may be the total area of the first surface and / or the total area of the second surface. In each case, independently of one another, the composition can be applied to a first surface (in particular an area of the first surface) of the metal foil with a thickness of at least 1 μm and at most 500 μm (in particular a thickness of at least 5 μm and at most 400 μm, in particular a thickness of at least 10 μm and at most 300 μm, in particular a thickness of at least 20 μm and at most 250 μm, in particular a thickness of at least 50 μm and at most 200 μm, in particular a thickness of at least 75 μm and at most 150 μm, in particular a thickness of at least 100 μm and at most 125 μm), and the composition or a further composition can be applied to a second surface (in particular an area of the second surface) of the metal foil.
[0099] Prior to step c), the metal foil may be heated to a first pretreatment temperature in the range of 170°C to 220°C and maintained for at least 1 minute, in particular at least 2 minutes, in particular at least 3 minutes, and at most 2 hours, in particular at most 1 hour, in particular at most 30 minutes, in particular at most 20 minutes, in particular at most 10 minutes, in particular at most 8 minutes, in particular at most 5 minutes. The inventors of the present invention have found that heating the metal foil to the first pretreatment temperature results in the removal of organic residues present on the metal foil, which is a result of its standard production process (such as rolling). The removal of organic residues from the first surface and / or the second surface ensures effective sintering and relatively high wettability of the first surface and / or the second surface. After heating the metal foil to the first pretreatment temperature, the metal foil may be cooled to a second pretreatment temperature in the range of 15°C to 40°C, in particular 20°C to 30°C. Cooling may be performed by active cooling, but is typically passive cooling, i.e. allowing the coated metal foil to cool to the second pretreatment temperature (which is typically ambient temperature). Optionally, heating to the first pretreatment temperature and / or cooling to the second pretreatment temperature can be carried out in a reducing atmosphere, an inert atmosphere and / or a vacuum. This avoids oxidation of the first surface and / or the second surface of the metal foil during heating to the first pretreatment temperature and / or cooling to the second pretreatment temperature. The vacuum can be a relatively high vacuum of at least 10 mbar, in particular at least 1 mbar, in particular at least 0.3 mbar.
[0100] After applying the composition specified according to the invention and / or the further composition to the first surface and / or the second surface of the metal foil according to step c), an optional step d) can be carried out: the composition on the first surface and / or the second surface of the metal foil or the first surface and / or the second surface together with the composition or together with the composition and the further composition is heated to a pre-drying temperature in the range of 100°C to 160°C, in particular in the range of 110°C to 150°C, in particular in the range of 120°C to 140°C, in particular in the range of 125°C to 130°C.
[0101] Optionally, after applying the composition obtained in step b) to the first surface, the metal foil is heated to a pre-drying temperature in the range of 100°C to 160°C (particularly in the range of 110°C to 150°C, particularly in the range of 120°C to 140°C, particularly in the range of 125°C to 130°C) and maintained for at least 1 minute and at most 30 minutes, followed by a cooling step, applying the composition obtained in step b) or another composition on the second surface, and heating the metal foil to a pre-drying temperature in the range of 100°C to 160°C (particularly in the range of 110°C to 150°C, particularly in the range of 120°C to 140°C, particularly in the range of 125°C to 130°C) and maintained for at least 1 minute and at most 30 minutes.
[0102] The pre-drying temperature can be maintained for at least 30 seconds, in particular at least 1 minute, in particular at least 2 minutes, in particular at least 3 minutes, and at most 30 minutes, in particular at most 20 minutes, in particular at most 10 minutes, in particular at most 8 minutes, in particular at most 6 minutes, in particular at most 5 minutes, in particular at most 4 minutes. The heating to the pre-drying temperature and the maintenance of the pre-drying temperature according to the optional step d) can be carried out in a reducing atmosphere, an inert atmosphere and / or a vacuum.
[0103] During the optional step d), at least 70 % by weight (particularly at least 75 % by weight, particularly at least 80 % by weight, particularly at least 85 % by weight, particularly at least 90 % by weight, particularly at least 95 % by weight, particularly at least 99 % by weight) of the initial weight of organic binder and / or other organic binder and / or optional polar organic solvent or optional turpentine can be evaporated. Evaporation refers to that liquid organic binder and / or other organic binder and / or optional liquid polar organic solvent or optional turpentine are converted into their vapor respectively at a boiling temperature lower than the organic binder and / or other organic binder and / or lower than the boiling temperature of optional polar organic solvent or optional turpentine. If step d) is carried out in a vacuum, the evaporation of organic binder and / or other organic binder and / or optional polar organic solvent or optional turpentine is further increased. The initial weight of the organic binder and / or the further organic binder can be determined by weighing the organic binder and / or the further organic binder and / or the optional polar organic solvent or the optional turpentine before providing / preparing the composition and / or the further composition provided according to the invention and / or by mass spectrometry or thermogravimetric analysis before and after heating according to step d). Even if the optional polar organic solvent or the optional turpentine can evaporate completely during step d), in particular up to 30% by weight (in particular up to 25% by weight, in particular up to 20% by weight, in particular up to 15% by weight, in particular up to 10% by weight, in particular up to 5% by weight, in particular up to 1% by weight) of the initial weight of the organic binder and / or the further organic binder can remain in the coated metal foil, in particular in the composition and / or the further composition coated on the first surface and / or the second surface of the metal foil independently of each other. The residual organic binder and / or additional organic binder in the coated metal foil ensures that the thin sheet and / or additional thin sheet adheres well to the first surface and / or second surface of the metal foil. In addition, during the sintering process of the coated metal foil, the residual organic binder and / or additional organic binder has a reducing effect on the coated metal foil and can provide adhesion to place the coated foil on the surface and / or multiple surfaces of the solid substrate to be firmly bonded. The weight of the residual organic binder and / or additional organic binder in the coated metal foil can be determined by weighing the coated metal foil during or before and after heating according to optional step d) and / or by mass spectrometry or thermogravimetric analysis.
[0104] After the method according to the invention, in particular after step c), or optionally after step d), the coated metal foil produced by the method according to the invention can be applied in a method for forming a copper-containing interconnect layer between two solid substrates or between a solid substrate and a metal foil, the method comprising the following steps:
[0105] e) providing a coated metal foil according to the invention produced by the method according to the invention, providing a solid substrate or providing a first solid substrate and providing a second solid substrate,
[0106] f) applying the coated metal foil according to the invention to a solid substrate or a first solid substrate,
[0107] g) in the case of forming a copper-containing interconnect layer between two solid substrates, placing a second solid substrate on the coated metal foil according to the invention,
[0108] h) applying a bonding pressure to press the solid substrate and the coated metal foil or the first solid substrate and the second solid substrate against each other, wherein the bonding pressure may be at least 100 kPa, in particular 1 MPa, in particular at least 2.5 MPa, in particular at least 5 MPa, in particular at least 7.5 MPa, in particular at least 10 MPa, and at most 40 MPa, in particular at most 35 MPa, in particular at most 30 MPa, in particular at most 25 MPa, in particular at most 20 MPa, in particular at most 15 MPa,
[0109] i) heating the coated metal foil or the solid substrate or the first solid substrate and / or the second solid substrate together with the coated metal foil to a sintering temperature in the range of 200°C to 300°C, in particular in the range of 205°C to 275°C, in particular in the range of 210°C to 270°C, in particular in the range of 215°C to 265°C, in particular in the range of 220°C to 260°C, in particular in the range of 225°C to 255°C, in particular in the range of 230°C to 250°C, in particular in the range of 235°C to 245°C, and maintaining the sintering temperature and the bonding pressure until a copper-containing intermediate layer is formed between the solid substrate and the metal foil or the first solid substrate and the second solid substrate.
[0110] Applying the coated metal foil according to the invention to the solid substrate or the first solid substrate and / or placing the second solid substrate on the coated metal foil can be done manually, can be done by transfer, in particular by vacuum-mediated foil transfer or vacuum-mediated substrate transfer, or can be done by a pick-and-place machine.
[0111] The sintering temperature and the bonding pressure can be maintained for at least 1 second, in particular at least 5 seconds, in particular at least 30 seconds, in particular at least 1 minute, in particular at least 3 minutes, in particular at least 4 minutes, and at most 30 minutes, in particular at most 15 minutes, in particular at most 10 minutes, in particular at most 8 minutes, in particular at most 5 minutes.
[0112] The method for forming a copper-containing intermediate layer between two solid substrates or between a solid substrate and a metal foil may further comprise a step j): cooling the copper-containing intermediate layer obtained in step i) between the first solid substrate and the second solid substrate or between the solid substrate and the metal foil, or the solid substrate, or the first solid substrate and / or the second solid substrate, together with the copper-containing intermediate layer obtained in step i) to a cooling temperature, said cooling temperature being in the range of 15° C. to 40° C., in particular in the range of 20° C. to 30° C. The cooling temperature may be ambient temperature. The cooling according to step j) may be carried out by active cooling, but is typically passive cooling, i.e. by cooling the copper-containing intermediate layer or the solid substrate or the first solid substrate and / or the second solid substrate together with the copper-containing intermediate to a cooling temperature, typically ambient temperature.
[0113] At least step c) of the method according to the invention, in particular at least steps b) and c), in particular at least steps a) to c), can be carried out in a reducing atmosphere, an inert atmosphere and / or a vacuum. Optionally, step d) of the method according to the invention can be carried out in a reducing atmosphere, an inert atmosphere and / or a vacuum. At least step i) of the method for forming a copper-containing intermediate layer between two solid substrates, in particular at least steps i and h), in particular at least steps g) to i), in particular at least steps f) to i), in particular steps e) to i), can be carried out in a reducing atmosphere, an inert atmosphere and / or a vacuum. Optionally, step j) can be carried out in a reducing atmosphere, an inert atmosphere and / or a vacuum.
[0114] In each case, the reducing atmosphere can be provided independently of one another by a mixture of evaporated formic acid and nitrogen or by a gas mixture of hydrogen and an inert gas. The gas mixture of hydrogen and an inert gas can be a gas mixture of nitrogen and hydrogen, or a gas mixture of argon and hydrogen. In each case, the inert atmosphere can be provided independently of one another by an inert gas. An inert gas can be included in an inert gas mixture. An inert gas can be nitrogen, carbon dioxide, helium, neon or argon. An inert gas mixture can be a mixture of at least two of nitrogen, carbon dioxide, helium, neon and argon.
[0115] The inventors of the present invention have found that the coated metal foil according to the present invention provides relatively good copper bond conductivity after sintering due to relatively low oxide impurities. The oxide impurities are so low that a reducing atmosphere does not need to be applied during sintering.
[0116] The pressure of the vacuum can in each case be, independently of one another, a pressure in the range of 0.1 mbar to 10 mbar, in particular in the range of 0.5 mbar to 5 mbar, in particular in the range of 1 mbar to 3 mbar. The inventors of the present invention have found that, due to the vacuum-induced reduction in the boiling point of the organic binder and / or the further organic binder and / or the optional polar organic solvent or the optional turpentine, sintering in a vacuum leads to further evaporation of the organic binder and / or the further organic binder and / or the optional polar organic solvent or the optional turpentine at relatively low temperatures. The further evaporation of the organic binder and / or the further organic binder and / or the optional polar organic solvent or the optional turpentine further increases the sintering efficiency of the coated metal foil according to the invention and facilitates sintering at relatively low sintering temperatures.
[0117] During step e), at least 70% by weight (in particular at least 75% by weight, in particular at least 80% by weight, in particular at least 85% by weight, in particular at least 90% by weight, in particular at least 95% by weight, in particular at least 99% by weight, in particular 100% by weight) of the initial weight of the organic binder and / or the further organic binder (in particular the residual organic binder and / or the residual further organic binder, and / or the optional polar organic solvent or the optional turpentine) can be evaporated. If the optional step d) has been carried out before step e), the residual organic binder and / or the residual further organic binder can be completely evaporated during step e. The initial weight of the organic binder and / or the further organic binder can be determined by weighing the organic binder and / or the further organic binder before providing / preparing the composition and / or the further composition specified according to the invention. The evaporation of the organic binder and / or the further organic binder (in particular the residual organic binder and / or the residual further organic binder) can be determined by weighing the first solid substrate and / or the second solid substrate together with the coated metal foil according to the invention during or before and after heating according to step e) and / or by mass spectrometry or thermogravimetric analysis.
[0118] The first solid substrate may be made of or composed of a metal or a metal oxide, and the second solid substrate may be made of or composed of a metal, another metal, a metal oxide, another metal oxide, or a surface mounted device component. The metal and / or another metal may be in the form of another foil. The metal or another metal may be gold, silver, nickel, palladium, copper, pretreated copper, or tin. The metal oxide or another metal oxide may be aluminum oxide. The surface mounted device component may be a capacitor, a chip resistor, a crystal oscillator, a diode, a fuse, an inductor, an integrated circuit, an LED, a network resistor, a transformer, a transistor, a silicon carbide (SiC) device, or a gallium nitride (GaN) device. The diode may be a silicon diode. The transistor may be a metal-oxide semiconductor field-effect transistor (MOSFET). The inventors of the present invention have found that an organic binder and / or another organic binder (particularly a residual organic binder and / or a residual other organic binder) may also reduce oxides on the first solid substrate and / or the second solid substrate. The coated metal foil according to the invention thus ensures sintering on copper, silver and / or nickel substrates even if these substrates are covered with oxide layers, in particular oxide layers of Cu 2 O.
[0119] Pretreated copper can be pretreated by, for example, coating the copper substrate with an organic surface protection (OSP) layer, wherein the OSP layer protects the copper from oxidation and dissolves during the soldering process. Alternatively, other methods (such as sol-gel application or CVD) can be used to coat the copper substrate with a protective layer to protect the copper from oxidation.
[0120] The present invention further relates to the use of the coated metal foil according to the present invention for forming a copper-containing intermediate layer / interconnect layer between two surfaces of a solid substrate (i.e. between the surface of a first solid substrate and another surface of a second solid substrate or between a solid substrate surface and a metal foil), in particular for chip bonding in microelectronic packaging, electric vehicle technology, hybrid electric vehicle technology, high-power electronic packaging, thick film technology, large-area bonding and / or battery applications. In particular, the present invention relates to the use of the coated metal foil according to the present invention for chip bonding. The present invention further relates to the use of the coated metal foil according to the present invention for forming a conductive path on a solid substrate. The conductive path on the solid substrate may be an electrically conductive path and / or a thermally conductive path on the solid substrate. The present invention further relates to the use of the coated metal foil according to the present invention for substrate bonding. The microelectronic package may be a WBG semiconductor package. The high-power electronic package may be a high-power light-emitting diode package. The inventors of the present invention have found that the use of the coated metal foil according to the present invention for forming a copper-containing intermediate layer / interconnection layer between two solid substrates or for forming a conductive path on a solid substrate ensures that the solid substrate and any electronic components (especially surface mount device components as described above when forming an interconnection layer or a conductive path on the solid substrate) have a relatively low thermal load. This is due to the relatively low sintering temperature required to sinter the coated metal foil according to the present invention.
[0121] If the coated metal foil according to the present invention is used to form an electrically conductive and / or thermally conductive path on a solid substrate, the solid substrate may be any substrate defined as a first substrate or a second substrate or a solid substrate as described above, as long as it is not an electrically conductive first substrate or a second substrate. If the coated metal foil according to the present invention is used for substrate bonding, the substrate may be any substrate defined as a first substrate or a second substrate as described above, an aluminum substrate (particularly a metallized aluminum substrate, particularly a copper metallized aluminum substrate), a ceramic substrate (particularly a metallized ceramic substrate, particularly a copper metallized ceramic substrate), a directional bonded copper substrate or a polymer substrate (particularly a polyimide substrate).
[0122] All features indicated in the description are to be understood as features applicable to all embodiments of the invention. This means, for example, that features specific to the coated metal foil according to the invention may also be applied to the composition specified according to the invention, to the method for producing a coated metal foil according to the invention, to the method for forming a copper-containing intermediate layer between a first solid substrate and a second solid substrate according to the invention and / or to the use according to the invention, and vice versa. Furthermore, unless otherwise indicated, the term "average" always means "arithmetic average", and the term "mean" always means "arithmetic mean". The abbreviation "wt.%" means "percentage by weight". The abbreviation "v / v" means "volume ratio".
[0123] The present invention will be explained in more detail with reference to the following drawings and embodiments.
[0124] Figure 1 SEM image showing a cross section of a copper sheet containing internal pores,
[0125] Figure 2 SEM image showing a cross section of a copper sheet having a multi-layered laminar structure,
[0126] Figure 3 a and Figure 3 b shows a scanning transmission electron microscopy image of a multilayered structure,
[0127] Figure 4 shows a SEM image of a foil according to the invention,
[0128] Figure 5 Another magnification is shown Figure 4 SEM image of the foil,
[0129] Figure 6 Another magnification is shown Figure 4 SEM image of the foil,
[0130] Figure 7 shows an SEM image of another foil coated with a thin layer of flakes according to the invention,
[0131] Figure 8 Another magnification is shown Figure 7 SEM image of the foil,
[0132] Fig. 9 shows a focused ion beam scanning electron microscope (FIB-SEM) image of another foil coated with a thin layer of flakes according to the invention,
[0133] Fig.10 Another magnification is shown Fig. 9 The cropping pattern of the image,
[0134] Fig.11 A FIB-SEM image of another foil coated with a thin flake thick layer according to the invention is shown,
[0135] Fig.12 A SEM image showing a cross section of an interconnection between a chip and a copper substrate, the interconnection being sintered from a coated copper foil according to the present invention,
[0136] Fig.13 A SEM image showing a cross section of an interconnection between a copper foil and a copper substrate, the interconnection being sintered from the coated copper foil according to the present invention, and
[0137] Fig.14 An SEM image of a cross section of an interconnect between two ceramic substrates sintered from a coated metal foil is shown.
[0138] Example 1: Average intragranular pore density and average intergranular cavity density of copper sheets
[0139] The composition according to the present invention comprises a thin sheet containing internal pores. For example, these thin sheets containing internal pores can be purchased as Cubrotec 8001 copper thin sheets provided by Carl Schlenk SE of Germany. The cross section of Cubrotec 8001 copper thin sheets is as follows: Figure 1 As shown. Figure 1 In FIG. 1 , many internal pores of the copper flakes are schematically shown by filled arrows. The voids between the flakes resulting from the intergranular cavities after sintering are schematically shown by unfilled arrows.
[0140] from Figure 1 It can be seen that the Cubrotec 8001 copper flakes have a relatively large number of internal pores and a relatively high average intragranular pore density. The average intragranular pore density of the Cubrotec 8001 copper flakes is 30 internal pores / μm 2 The space between Cubrotec8001 copper sheets is 40%.
[0141] Embodiment 2: Copper sheet or copper alloy sheet having a multi-layer structure
[0142] If the flake is Cubrotec 8001 copper flake, the flake has a multi-layered structure. Cubrotec 8000 flake has only a layered structure, not a multi-layered structure. Figure 2 A cross section of a Cubrotec 8001 copper sheet is shown, showing the multi-layered structure of the copper sheet. Figure 2In the figure, the stacked multilayer structure of three copper sheets is exemplarily shown by the white dashed frame. Each multilayer structure is composed of a different number of thin layers in the range of 2 to 20 thin layers. In addition, the total thickness of the multilayer structure varies in the range of 20nm to 400nm.
[0143] exist Figure 3 a and Figure 3 In b, a scanning transmission electron microscope (STEM) image of a multilayer structure consisting of 10 thin layers is shown as an example. Figure 3 In a, the lamellar boundaries between the thin layers (thin layers 1 to 10) in the stacked multilayer laminar structure are exemplarily shown by black dashed lines. In this regard, for example, thin layer 1 is in contact with thin layer 2 via one lamellar boundary. However, thin layer 2 is in contact with thin layer 1 and thin layer 3 via one lamellar boundary each, and so on. This results in a stacked multilayer laminar structure consisting of thin layers in contact with each other. In addition, in Figure 3 In b, the nanocrystalline structure of copper forming thin layers in a stacked multilayer structure is shown.
[0144] Example 3: Composition
[0145] The following composition was used for the test:
[0146] Table 1: Composition
[0147]
[0148]
[0149] Table 1 shows different compositions that can be coated on the first surface and / or the second surface of a copper foil or a copper alloy foil. In each of Composition No. 1 to Composition No. 12, Cubrotec 8001 copper particles are exemplarily used. As can be seen from Table 1, Composition No. 1 and Composition No. 2 do not contain copper flakes coated with stearic acid. Composition No. 3 to Composition No. 12 contain copper flakes coated with stearic acid. In Composition No. 2, isopropyl alcohol is exemplarily used as an optional polar organic solvent. In Composition No. 4, acetone is exemplarily used as an optional polar organic solvent. In Composition No. 6, optional turpentine is used.
[0150] In each of Composition No. 3, Composition No. 5, and Composition No. 7 to Composition No. 12, the total weight of the copper flakes coated with stearic acid is in the range of 60 wt% to 76 wt% relative to the total weight of the composition. The total weight of the copper flakes coated with stearic acid includes the total weight of the stearic acid coated on the copper flakes and the total weight of the copper flakes. For example, in Composition No. 3, 60 wt% of the copper flakes coated with stearic acid contain 58.5 wt% of the copper flakes and 1.5 wt% of the stearic acid coated on the copper flakes. Therefore, the total content of solids in Composition No. 3 is 58.5 wt%. In addition, the organic binder in Composition No. 3 is a mixture of ethylene glycol and α-terpineol. In this regard, the total weight of ethylene glycol is 16 wt% relative to the total weight of the composition, and the total weight of α-terpineol is 24 wt% relative to the total weight of the composition. Therefore, the total weight of the organic binder contained in Composition No. 3 is 40 wt% relative to the total weight of the composition.
[0151] Example 4: Production of composition
[0152] Hereinafter, the preparation of composition No. 1 and composition No. 5 is exemplarily shown. The preparation of composition No. 1 includes the following steps:
[0153] In a commercially available standard paste mixing tank for speed mixer and planetary mixer, 63 grams of copper flakes were added. Subsequently, 37 g of ethylene glycol was added to the copper flakes as an exemplary organic binder. In a planetary rotary mixer, the mixture was mixed at 1000 rpm for 4 minutes and then at 500 rpm for 5 minutes. Alternatively, the mixture can also be mixed at 1500 rpm for 30 seconds in a speed mixer.
[0154] The preparation of composition No. 5 comprises the following steps:
[0155] 15.5 g of ethylene glycol, 24 g of α-terpineol and 0.5 g of PEG 600 were mixed in a beaker with a magnetic stirrer at 500 rpm for 3 minutes. Thus, an organic binder was obtained. In a planetary rotary mixer, 60 g of stearic acid-coated copper flakes, i.e., flakes coated with a stearic acid coating of up to 1.5% by weight, were added. Subsequently, the above organic binder was added to the coated copper flakes and mixed in a planetary rotary mixer at 1000 rpm for 4 minutes and at 500 rpm for 5 minutes.
[0156] Example 5: Pretreatment of copper foil
[0157] Copper foil with a thickness of 10 μm was purchased from Schlenk Metallfolien GmbH & Co. KG. Since the foil was produced by a conventional rolling process, there was oily residue on its surface. In order to remove the oily residue, the foil was pretreated as follows:
[0158] The foil was cut into pieces of 50 mm x 50 mm. Each piece was placed on a hot plate at 25 ° C in a reflow oven RSS-160-S of UniTemp GmbH, Luitpoldstr. 6, D-85276 Pfaffenhofen, Germany. The oven was then closed, a vacuum of 1 mbar was applied, and then heated from 25 ° C to 180 ° C at 60 K / s, and the vacuum and temperature were maintained for 30 minutes. Finally, the oven with the foil was cooled to 25 ° C at 30 K / min under vacuum. Finally, the vacuum was released by introducing nitrogen into the oven before removing the foil. After these steps, there was no organic oily residue on both sides of the foil and it could be used for spraying as described below.
[0159] Example 6: Spraying of pretreated copper foil
[0160] As shown in Examples 3 and 4, each of Compositions No. 2 to No. 7 was applied independently of one another to the first surface and / or the second surface of a separate pretreated copper foil by spraying. Each of Composition No. 1 and Composition No. 8 to No. 12 was applied independently of one another to the first surface and / or the second surface of a separate pretreated copper foil by manual coating, as shown below:
[0161] Spraying was carried out using SM300OMEGAX-3A-SS, SHOTMASTER 300OMEGAX from MUSASHI ENGINEERING EUROPEGMBH, Mar-cel-Breuer-Str. 15, 80807 Munich, Germany. The following spraying parameters were applied:
[0162] Nozzle opening 100-120μm (spiral valve mechanism)
[0163] The air pressure is:
[0164] Box inlet – 0.3MPa-0.4MPa
[0165] Chamber – 0.3MPa
[0166] Nozzle – 0.4MPa-0.5MPa
[0167] Spray coating was performed by printing a 30 mm line with a 0.5 mm pitch at a coating speed of 200 mm / s.
[0168] Although spraying is exemplarily shown as the application method, other application methods such as aerosol jet printing, screen printing, or material dispensing are also performed in other embodiments to apply the composition to the first surface and / or the second surface of the copper foil.
[0169] For composition No. 1 and composition No. 8 to composition No. 12, manual coating was performed with a metal extruder. This is due to the higher viscosity of these formulations, which does not allow a spraying process due to the absence of polar organic solvents. In this case, the formulations were applied to the edge of the foil and manually spread over the entire surface of the foil by a single pass with a handheld metal extruder to obtain a uniform layer on the foil.
[0170] Example 7: Preparation of coated copper foil by sintering
[0171] After spraying and manual coating, the foil is first subjected to a pre-drying step and then to a sintering step as follows:
[0172] Pre-drying is carried out in a hot air sterilizer SN30 from Memmert GmbH + Co. KG, Aeussere Rittersbacher Strasse 38, 91126 Schwabach, Germany. For this purpose, the sterilizer is preset to 120°C and once the temperature has been reached, the coated foil is placed in the oven while running at 100% fan speed for 5 minutes. The door of the sterilizer is then opened and the foil is removed from the oven at 120°C and allowed to cool to room temperature in the open air. Thus, the foil is pre-dried using a hot-in / hot-out process. This pre-drying leads to the evaporation of the organic binder. However, residual organic binder remains on each coated copper foil, which ensures that the flakes adhere to the first surface and / or the second surface of the copper foil, respectively. After this step, sintering is carried out as follows.
[0173] To obtain Figures 4 to 11 The foil shown in was sintered under pressureless conditions in a reflow oven RSS-160-S from UniTemp GmbH at 250°C under nitrogen for 30 minutes as follows:
[0174] The pre-dried foil was placed on the hot plate of a reflow oven at 25°C and the oven was closed. A vacuum of 1 mbar was applied at 25°C. Then, nitrogen was flowed into the chamber for 1 minute at 25°C. The oven was then ramped up to 250°C at 30 K / s under nitrogen, then kept at 250°C for 30 minutes under nitrogen, then cooled to 25°C at a rate of 30 K / s under nitrogen, and the sintered foil was then removed.
[0175] The foil was examined by SEM and FIB-SEM. Figures 4 to 11 shown.
[0176] exist Figure 4 In the , the flakes show their potential to uniformly cover the copper foil area. Figure 5In FIG. 1 , the arrows indicate the sintered connections in the form of sintered necks between the sheets. This shows that the sheets exhibit very good sintering capabilities even under pressureless conditions at 250° C. in an inert atmosphere for 30 minutes.
[0177] Figure 6 The thin slices show a very fine grain structure on the surface. Electron backscatter diffraction (EBSD) analysis of the grain structure shows that the orientation of the
[101] grains relative to the surface normal is preferred.
[0178] Figure 7 and Figure 8 The copper foil is shown covered by a thin layer of foil, such that portions of the copper foil remain uncoated. Figure 7 The arrows added in point to the uncoated part of the copper foil.
[0179] Fig. 9 A single layer of flakes sintered onto copper foil is shown. The grain size on the flakes is significantly lower than that on the foil. Fig. 9 It can be clearly seen that the grains on the foil are significantly larger (combined with Figure 3 It can be seen that the grains on the flakes are in the range of <50 nm), thus creating a large energy gradient between the flakes and the foil. This ensures accelerated material transport by surface diffusion and the formation of sintering necks even under pressureless conditions, such as Fig.10 It can be clearly observed from Fig.12 , Fig.13 and Fig.14 As can be seen in FIG. 1 , it is shown that uniform application of bonding pressure increases the contact area between the thin sheet and the foil, thereby improving the bonding between the thin sheet and the copper foil. Fig.10 The added arrows point to the sintering bridges formed between the flakes and the foil.
[0180] Fig.11 It was shown that the flakes can be stacked on top of each other and connected to each other by sintering.Thus, the flakes offer the potential to form thin and uniform coatings on foils.
[0181] To prepare Fig.12 For the sample shown, the top of the copper foil (i.e. the interface of the chip) was coated by spraying as described above because a thin layer was required. However, at the bottom (i.e. the interface of the substrate), a thick sintered layer was required between the foil and the substrate. To achieve this, a thick layer of Composition No. 1 was printed directly onto the bottom of the copper foil using the manual coating process described above after pre-drying the sprayed layer. After this process, the manually applied layer was also pre-dried, and the foil with a thin sprayed and pre-dried layer on one side and a thick manually applied and pre-dried layer on the other side was then used as a sandwich to bond the chip to the bare copper substrate.
[0182] Fig.12SEM images of cross sections of sintered interconnects are shown, demonstrating the possibility of applying different sintering paste thicknesses on either side of the foil and sintering the test chips onto a bare copper substrate. Sintering was performed at 275°C for 5 minutes at a bonding pressure of 1 MPa in an SP300 sintering machine from budatec GmbH, Melli Beese Straβe 28, 12487 Berlin, Germany (as shown in sample No. 5 in Table 1 below) in an inert atmosphere.
[0183] Fig.13 A SEM image of a cross section of a sintered interconnect is shown, demonstrating the possibility of bonding just the foil to a bare copper substrate. Sintering was performed at 275°C for 5 minutes at a bonding pressure of 1 MPa.
[0184] To prepare Fig.14 The sample shown is prepared by applying the composition to the first surface of the copper foil with a thickness of 20 μm and applying the composition to the second surface of the copper foil with a thickness of 75 μm, and then pre-drying. As described above, the composition No. 1 is applied manually. The paste is first applied to one side and pre-dried in air at 120 ° C for 5 minutes, and then the composition is applied to the other side and pre-dried in air at 120 ° C for 5 minutes again. Finally, the double-sided coated metal foil is placed on the first ceramic substrate by a pick-and-place machine for precise placement. Then, the second ceramic substrate with copper end metallization is placed on the coated metal foil by a pick-and-place machine for precise placement. Subsequently, on a Fineplacer Sigma flip-chip bonder from Finetech GmbH & Co. KG, Box-berger Str. 14, 12681 Berlin, at 260 ° C, in an open bonding chamber with a nitrogen flow rate of 3 L / min and a lifting rate of 1 K / s, sintering is performed for 3 minutes under a 2MPa bonding pressure applied on the second substrate. The resulting interconnect cross section is shown in Fig.14 shown.
[0185] from Fig.14 It can be seen that by sintering, the composition layer between the first ceramic substrate and the copper foil and between the second ceramic substrate and the copper foil is reduced to a thickness of 10 μm to 15 μm and 30 μm to 40 μm, respectively. The coated metal foil sintered between the ceramic substrates shows uniform and regular interconnection.
[0186] Example 8: Performing a shear test
[0187] According to the present invention, the foil will have a 1 mm 2The imprinted Au-terminated metallized dummy test chip was sintered onto a bare copper substrate. Ten samples were prepared for each test. A foil with a thin sintered layer of less than 5 μm was prepared on each side of a 10 μm thick copper foil from Schlenk Metallfolien GmbH & Co. KG. Sintering was performed in an SP300 sintering machine from budatec GmbH under an inert nitrogen atmosphere. After sintering, shear tests were performed according to the MLT-STD-883 test method (Mechanical Test Method 2019.5 Chip Shear Strength). The arithmetic mean shear strength values of the sintered interconnects were measured by an XYZ Condor Sigma Lite shear tester at a shear speed of 100 μm / s. The results are given in Table 3 below.
[0188] Table 2
[0189]
[0190]
[0191] Although only copper foil and copper sheet experiments are shown above as examples, these experiments can also be performed with bronze foil, brass foil, bronze sheet and brass sheet. All these experiments give similar results to the above experiments.
Claims
1. A coated metal foil, the coated metal foil being used to form a copper-containing intermediate layer between a first solid substrate and a second solid substrate or between a solid substrate and the metal foil, wherein: The coated metal foil comprises or consists of: Copper metal foil or first copper alloy metal foil or copper metal foil plated with nickel-iron alloy, wherein the metal foil has a first surface and a second surface and a composition coated on the first surface and / or the second surface of the metal foil, Wherein, the composition comprises or consists of the following components: Organic binders, and a sheet of copper, the first copper alloy or the second copper alloy, Wherein, the sheet comprises internal pores.
2. The coated metal foil according to claim 1, wherein The composition is applied on the first surface, and another composition is applied on the second surface, Wherein, the additional composition comprises or consists of: the organic binder or another organic binder, and A sheet of copper, the first copper alloy, or the second copper alloy, or an additional sheet, wherein the additional sheet comprises internal pores.
3. The coated metal foil according to claim 1 or 2, wherein: The average intragranular pore density of the thin sheet of copper, the first copper alloy or the second copper alloy and / or the further thin sheet is 7 internal pores / μm 2 Up to 30 internal pores / μm 2 within the range.
4. A coated metal foil according to any one of the preceding claims, wherein The grains in the metal foil at the first surface and / or the second surface of the metal foil have an average grain size of at least 2 μm and at most 100 μm, and / or, The grains in the flakes and / or the further flakes independently of one another have an average grain size of at least 20 nm and at most 200 nm, and / or, wherein the ratio of the average grain size of the grains in the sheet to the average grain size of the grains at the first surface and / or the second surface of the metal foil does not exceed 0.002 in each case, and / or, The ratio of the average grain size of the grains in the additional sheet to the average grain size of the grains at the second surface of the metal foil does not exceed 0.
002.
5. The coated metal foil according to any one of the preceding claims, in, The first copper alloy is bronze or brass, and / or, Therein, the thickness of the metal foil is at least 5 μm and at most 150 μm, in particular at most 100 μm.
6. The coated metal foil according to any one of the preceding claims, in, The sheet and / or the further sheet is a sheet of the second copper alloy, and the second copper alloy is bronze or brass, and / or, Therein, the flakes and / or the further flakes have an average particle size D50 of at most 5 μm, determined by laser particle size analysis.
7. A coated metal foil according to any one of the preceding claims, wherein The sheet and / or the further sheet has a multi-layered layer structure.
8. The coated metal foil according to any one of the preceding claims, in, The flakes and / or the further flakes are coated with stearic acid, Therein, the total weight of the stearic acid relative to the total weight of the flakes coated with stearic acid and / or the total weight of the stearic acid relative to the total weight of the further flakes coated with stearic acid is in each case independently of one another at most 1.5% by weight.
9. A coated metal foil according to any one of the preceding claims, wherein The organic binder and / or the further organic binder are in each case independently of one another terpineol, a primary alcohol, a diol, a triol, a polymeric diol, or a mixture of at least two of terpineol, a primary alcohol, a diol, a triol and a polymeric diol.
10. A coated metal foil according to any one of the preceding claims, wherein The composition and / or the further composition independently of one another further comprises turpentine or a polar organic solvent, in particular an alcohol, acetone or a mixture of an alcohol and acetone.
11. The coated metal foil according to any one of the preceding claims, in, 10% to 100%, in particular 50% to 100%, of the area of the first surface of the metal foil and / or the area of the second surface of the metal foil are independently coated with the composition, and / or, wherein the composition is applied to the first surface and / or the second surface of the metal foil, in each case independently of one another, in a thickness of at least 1 μm and at most 500 μm, in particular in a thickness of at least 1 μm and at most 50 μm, or wherein 10% to 100%, in particular 50% to 100%, of the area of the first surface of the metal foil is coated with the composition, and 10% to 100%, in particular 50% to 100% of the area of the second surface of the metal foil is coated with the additional composition, and / or Therein, the composition is applied to the first surface of the metal foil and the further composition is applied to the second surface of the metal foil, in each case independently of one another, with a thickness of at least 1 μm and at most 500 μm, in particular with a thickness of at least 1 μm and at most 50 μm.
12. A method for producing a coated metal foil according to any one of the preceding claims, comprising the steps of: a) Provide: - a metal foil of copper or a first copper alloy or copper plated with a nickel-iron alloy, wherein the metal foil has a first surface and a second surface, - said sheet and / or said optional further sheet of copper or said first copper alloy or said second copper alloy, wherein said sheet and said further sheet contain internal pores, and - an organic binder and optionally said further organic binder, b) mixing said flakes and said organic binder to obtain a composition, and optionally mixing said flakes or said further flakes and said organic binder or said further organic binder to obtain a further composition, and c) applying the composition obtained in step b) to the first surface and / or the second surface of the metal foil, or applying the composition obtained in step b) to the first surface of the metal foil and applying the additional composition obtained in step b) to the second surface of the metal foil to obtain the coated metal foil.
13. The method according to claim 12, in, The metal foil is bronze or brass, and / or, The metal foil has a thickness of at least 5 μm and at most 150 μm, in particular at most 100 μm, and / or The sheet and / or the further sheet is a sheet of the second copper alloy, and the second copper alloy is bronze or brass, and / or, The flakes and / or further flakes have an average particle size D50 of at most 5 μm, as determined by laser granulometry, and / or, The sheet and / or the further sheet has a multi-layered structure, and / or, The flakes and / or the further flakes are coated with stearic acid, wherein the total weight of stearic acid, relative to the total weight of the flakes coated with stearic acid and / or relative to the total weight of the further flakes coated with stearic acid, is in each case independently of one another at most 1.5% by weight, and / or, The organic binder and / or the further organic binder are in each case independently of one another terpineol, a primary alcohol, a diol, a triol, a polymeric diol, or a mixture of at least two of terpineol, a primary alcohol, a diol, a triol and a polymeric diol.
14. The method according to claim 12 or 13, wherein: Prior to step c), the metal foil is heated to a first pretreatment temperature in the range of 170°C to 220°C for at least 1 minute and at most 2 hours, and cooled to a second pretreatment temperature in the range of 15°C to 40°C.
15. The method according to any one of claims 12 to 14, in, After step c), the metal foil is heated to a pre-drying temperature in the range of 100° C. to 160° C. for at least 1 minute and at most 30 minutes, or wherein, during step c) and after applying the composition obtained in step b) to the first surface, the metal foil is heated to a pre-drying temperature in the range of 100°C to 160°C for at least 1 minute and at most 30 minutes, followed by a cooling step, applying the composition obtained in step b) or the further composition to the second surface and heating the metal foil to the pre-drying temperature in the range of 100°C to 160°C for at least 1 minute and at most 30 minutes.
16. Use of the coated metal foil according to any one of claims 1 to 11 for forming a copper-containing intermediate layer between two surfaces of a solid substrate or between a surface of a solid substrate and the metal foil to form a conductive path on a solid substrate or for substrate bonding.
Citation Information
Patent Citations
Nanometer conductive ink and preparing method thereof
CN104341860A
Method of forming a metal trace
US20060258136A1
Maskless direct write of copper using an annular aerosol jet
WO2006041657A2